Cathode active material for lithium ion batteries
Patent Information
- Application Number
- CN202211165138.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2016-03-14
- Filing Date
- 2017-03-14
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2037-03-14
Smart Images

Figure CN115394997B_ABST
Abstract
Description
[0001] This application is a divisional application of the invention patent application with the international filing date of March 14, 2017, which entered the Chinese national phase on August 30, 2018, with Chinese national application number 201780014413.7 and the invention title "Cathode Active Material for Lithium-ion Batteries".
[0002] Cross-references to related applications
[0003] Pursuant to 35 USC §119(e), this application claims the benefit of the following patents: U.S. Provisional Patent Application Serial No. 62 / 307,956, entitled “Surface-Modified Cathode Active Material for Lithium-Ion Batteries,” filed March 14, 2016; and U.S. Patent Application Serial No. 62 / 307,964, entitled “Cathode Active Material for Lithium-Ion Batteries,” filed March 14, 2016. The entire contents of each patent application are incorporated herein by reference. Technical Field
[0004] This disclosure relates generally to batteries, and more specifically to cathode active materials for lithium-ion batteries.
[0005] U.S. government licensing rights
[0006] This invention is based on WFO Proposal No. 85F59 and was carried out with the support of the U.S. government. This invention is based on CRADA 1500801 between Apple Inc. and Argonne National Laboratory (part of the U.S. Department of Energy). The U.S. government owns certain rights to this invention. Background Technology
[0007] Commonly used rechargeable battery types are lithium batteries, such as lithium-ion or lithium-polymer batteries. As battery-powered devices become smaller and more powerful, the batteries powering these devices need to store more energy in a smaller volume. Therefore, mechanisms that can improve the volumetric energy density of batteries in devices can facilitate the use of battery-powered devices.
[0008] Lithium transition metal oxides can be used in the cathode active materials of lithium-ion batteries. These compounds may include lithium cobalt oxides or derivatives thereof. These compounds may be in powder form. Summary of the Invention
[0009] In a first aspect, this disclosure relates to compounds conforming to formula (III):
[0010] Li α Co 1-x M x Al γ Oδ (III)
[0011] wherein M is B, Na, Mn, Ni, Mg, Ti, Ca, V, Cr, Fe, Cu, Zn, Al, Sc, Y, Ga, Zr, Mo, Ru or a combination thereof, 0.95≤α≤1.10, 0<x<0.50, 0≤γ≤0.05, and 1.95≤δ≤2.60.
[0012] In some aspects, M is Mn, Ni or a combination thereof, 0.95≤α≤1.10, 0<x<0.50, 0≤γ≤0.05, and 1.95≤δ≤2.60.
[0013] In another aspect, the present disclosure relates to a powder comprising particles. The particles comprise a compound conforming to Formula (III).
[0014] In another aspect, the present disclosure relates to a powder comprising particles having a core and a coating. The coating is disposed on at least a portion of the core. The core comprises a compound selected from the compounds of Formula (I), Formula (IIa), Formula (IIb) and Formula (III):
[0015] Li α MO δ (I)
[0016] (x)[Li2M 1 O3]·(1-x)[LiM 2 O2] (IIa)
[0017] (x)[Li2M 1 O3]·(1-x)[Li 1-y M 2 O2] (IIb)
[0018] Li α Co 1-x M x Al γ O δ (III)
[0019] wherein
[0020] when the compound is of Formula (I),
[0021] M is selected from Co, Mn, Ni and combinations thereof,
[0022] 0.95≤α≤2, and
[0023] 1.95≤δ≤3;
[0024] when the compound is of Formula (IIa),
[0025] 0≤x≤1,
[0026] M 1 Selected from Ti, Mn, Zr, Mo, Ru, and combinations thereof, and
[0027] M 2 Selected from B, Na, Mg, Ti, Ca, V, Cr, Mn, Fe, Co, Ni, Cu, Zn, Al, Sc, Y, Ga, Zr, Mo, Ru, and combinations thereof;
[0028] When the compound is of formula (IIb),
[0029] 0≤x≤1,
[0030] 0≤y≤1,
[0031] M 1 Selected from Ti, Mn, Zr, Mo, Ru, and combinations thereof, and
[0032] M 2 Selected from B, Na, Mg, Ti, Ca, V, Cr, Mn, Fe, Co, Ni, Cu, Zn, Al, Sc, Y, Ga, Zr, Mo, Ru, and combinations thereof; and
[0033] When the compound is of formula (III),
[0034] 0.95≤α≤1.10,
[0035] M is selected from B, Na, Mn, Ni, Mg, Ti, Ca, V, Cr, Fe, Cu, Zn, Al, Sc, Y, Ga, Zr, Mo, Ru, and combinations thereof.
[0036] 0 <x<0.50,
[0037] 0 ≤ γ ≤ 0.05, and
[0038] 1.95≤δ≤2.60.
[0039] In some respects, the compound is of formula (I).
[0040] M is selected from Co, Mn, Ni, and combinations thereof.
[0041] 1≤α≤2, and
[0042] 2≤δ≤3.
[0043] In some respects, the compound is of formula (IIa).
[0044] 0≤x≤1,
[0045] M 1Selected from Ti, Mn, Zr, Mo, Ru, and combinations thereof, and
[0046] M 2 Selected from B, Na, Mg, Ti, Ca, V, Cr, Mn, Fe, Co, Ni, Cu, Zn, Al, Sc, Y, Ga, Zr, Mo, Ru, and combinations thereof.
[0047] In some respects, the compound is of formula (IIa), and 0 <x≤0.10。
[0048] In some respects, the compound is of formula (IIb).
[0049] 0≤x≤1,
[0050] 0≤y≤1,
[0051] M 1 Selected from Ti, Mn, Zr, Mo, Ru, and combinations thereof, and
[0052] M 2 Selected from B, Na, Mg, Ti, Ca, V, Cr, Mn, Fe, Co, Ni, Cu, Zn, Al, Sc, Y, Ga, Zr, Mo, Ru, and combinations thereof.
[0053] In some respects, the compound is of formula (IIb), and 0 <x≤0.10。
[0054] In some respects, the compound is of formula (III).
[0055] 0.95≤α≤1.10,
[0056] M is selected from Mn, Ni, and combinations thereof.
[0057] 0 <x<0.50,
[0058] 0 ≤ γ ≤ 0.05, and
[0059] 1.95≤δ≤2.60.
[0060] The coating comprises oxide materials, fluoride materials, or combinations thereof.
[0061] In some aspects, the core comprises a compound conforming to formula (IIa). In some aspects, the core comprises a compound conforming to formula (IIb).
[0062] In some aspects, the core contains compounds conforming to formula (III). In other variations, 0.001 ≤ γ ≤ 0.03.
[0063] In one aspect, this disclosure relates to compounds represented by formula (IV):
[0064] Li α Co 1-x Mn x O δ (IV)
[0065] Where 0.95≤α≤1.10, 0≤x≤0.10, and 1.90≤δ≤2.20.
[0066] On the other hand, 0 <x≤0.10。
[0067] In another respect, this disclosure relates to compounds represented by formula (IV), wherein 0.98 ≤ δα ≤ 1.01.
[0068] In another aspect, this disclosure relates to compounds represented by formula (IV), wherein 1.00 ≤ α ≤ 1.05. In another aspect, 0 ≤ x ≤ 0.10.
[0069] In another respect, this disclosure relates to compounds represented by formula (IV), wherein 0.95 ≤ α ≤ 1.05 and 0.02 ≤ x ≤ 0.05.
[0070] In another respect, this disclosure relates to compounds represented by formula (IV), wherein 1.01 ≤ α ≤ 1.05 and 0.02 ≤ x ≤ 0.05.
[0071] In another respect, this disclosure relates to compounds represented by formula (IV), wherein 0.95 ≤ α ≤ 1.05 and x = 0.04.
[0072] In another respect, this disclosure relates to compounds represented by formula (IV), wherein 1.01 ≤ α ≤ 1.05 and x = 0.04.
[0073] In another respect, this disclosure relates to compounds represented by formula (IV), wherein 0.98 ≤ α ≤ 1.01 and x = 0.03.
[0074] On the other hand, the compound has a structure of formula (Va) or formula (Vb):
[0075] (x)[Li2MnO3]·(1-x)[LiCoO2] (Va)
[0076] (x)[Li₂MnO₃]·(1-x)[Li (1-y) Co (1-y) Mn y O2] (Vb)
[0077] Where 0 ≤ x ≤ 0.10, and optionally 0 ≤ y ≤ 0.10. In some variations, 0 <y≤0.10。
[0078] In some aspects, the present disclosure relates to a powder comprising particles, wherein the particles comprise a compound represented by Formula (IV): Li α Co 1-x Mn x O δ . In various aspects, 0.95≤α≤1.10, 0≤x≤0.10, and 1.90≤δ≤2.20. In various aspects, 0.95≤α≤1.10, 0<x≤0.10, and 1.90≤δ≤2.20. In some embodiments, at least a portion of the particles have a smooth surface. In various instances of these embodiments, at least a portion of the particles have a tap density equal to or greater than 2.2 g / cm 3 . In various instances of these embodiments, at least a portion of the particles have a smooth surface and a tap density equal to or greater than 2.2 g / cm 3 .
[0079] In another aspect, the present disclosure relates to a cathode active material comprising the powder described herein.
[0080] In another aspect, the present disclosure relates to a cathode having a cathode active material disposed on a current collector.
[0081] In another aspect, the present disclosure relates to a battery cell, which includes an anode having an anode current collector and an anode active material disposed on the anode current collector, as well as the cathode.
[0082] In another aspect, the present disclosure relates to a portable electronic device comprising a set of components driven by a battery pack.
[0083] In another aspect, the present disclosure relates to a method for preparing the powder described herein. First, a precursor solution (for example, an aluminum salt and / or fluoride salt precursor) is prepared by dissolving the precursor in a solvent to form the precursor solution. The precursor solution is added to a particle powder to form a wet-impregnated powder. The wet-impregnated powder is heated to an elevated temperature to form particles having the composition described herein.
[0084] In another aspect, a plurality of precursors (for example, an aluminum salt and a fluoride salt) are dissolved in a first solvent and a second solvent to form a first solution and a second solution, respectively. The first solution and the second solution are then mixed to prepare a precursor solution, which is then added to the particles as described herein.
[0085] In another aspect, the present disclosure relates to preparing particles by a dry mixing method. Particles of a nanocrystalline material are mixed with particles comprising the compound of Formula (IV). The nanocrystalline material particles and the particles comprising Formula (IV) are subjected to compressive force, shear force, or a combination thereof. The nanocrystalline material particles bond to the surfaces of the powder particles, which thereby form a coating on the powder particles.
[0086] In another aspect, the present disclosure relates to a compound represented by formula (VII) or formula (VIII):
[0087] Li α Co 1-x-y M y Mn x O δ (VII)
[0088] Li α Co 1-x-y Al y Mn x O δ (VIII)
[0089] When the compound is represented by formula (VII), in various aspects, M is at least one element selected from the group consisting of B, Na, Mg, Ti, Ca, V, Cr, Fe, Ni, Cu, Zn, Al, Sc, Y, Ga, Zr, Mo, and Ru. In some variations, 0.95≤α≤1.30, 0<x≤0.30, 0≤y≤0.10, and 1.98≤δ≤2.04. In various aspects, the compound is a compound having a single phase with a crystal structure. In further aspects, α>1+x and / or α<1+x.
[0090] In a further aspect, the present disclosure relates to a powder comprising particles. The average diameter of the particles may be at least 5 μm. In some aspects, the average diameter of the particles may be at least 20 μm. In some aspects, the particles may comprise secondary particles, each secondary particle comprising a plurality of primary particles sintered together. In some variations, at least 30% of the average secondary particles are formed from a single primary particle.
[0091] In a further aspect, the present disclosure relates to a cathode active material comprising the compound or the powder.
[0092] In a further aspect, the present disclosure relates to a battery cell, which includes an anode and a cathode comprising the cathode active material. In some aspects, the battery cell may have a first cycle discharge energy greater than or equal to 750 Wh / kg. In some aspects, the battery cell may have an energy retention rate greater than or equal to 70% after 10 charge-discharge cycles.
[0093] In some aspects, the battery cell may have an energy capacity retention rate of at least 65% after 52 discharge cycles. Brief Description of the Drawings
[0094] The present disclosure will be readily understood by the following detailed description taken in conjunction with the accompanying drawings, in which like reference numerals refer to like structural elements, and wherein:
[0095] Figure 1 A top view of a battery cell according to an exemplary embodiment;
[0096] Figure 2 A side view of a set of layers of a battery cell according to an exemplary embodiment;
[0097] Figures 3A to 3C A series of scanning electron micrographs according to exemplary embodiments are shown, which respectively illustrate a base powder, a base powder coated with 0.1 wt% AlF3, and a base powder coated with 0.1 wt% Al2O3;
[0098] Figure 4 A graph representing the performance data of three coin half-cells (each with a single cathode active material) during the first charge and discharge cycles, according to an exemplary embodiment;
[0099] Figure 5 To represent according to the exemplary implementation scheme Figure 4 A graph showing the change in capacity of four coin-sized half-cells with increasing cycles during rate testing;
[0100] Figure 6 To represent according to the exemplary implementation scheme Figure 4 A graph showing the change in capacity of four coin-sized half-cells with increasing cycles during life testing;
[0101] Figure 7 To represent according to the exemplary implementation scheme Figure 4 A graph showing the energy density of four coin-sized half-cells as a function of increasing cycles during rate testing.
[0102] Figure 8 To represent according to the exemplary implementation scheme Figure 4 A graph showing the change in energy density of four coin half-cells with increasing cycles during life testing;
[0103] Figure 9 For the corresponding rate test Figure 4 A graph showing the charging and discharging characteristics of each of the four coin-sized half-cells.
[0104] Figure 10 For the corresponding life test Figure 4 A graph showing the charging and discharging characteristics of each of the four coin-sized half-cells.
[0105] Figure 11 For the purpose of rate testing Figure 4 A graph showing the dQ / dV characteristic data for each of the four coin half-cells; and
[0106] Figure 12 To indicate the life test Figure 4 A graph showing the dQ / dV characteristic data for each of the four coin half-cells.
[0107] Figure 13 To represent the molar ratio containing Li according to the exemplary embodiment α Co 0.96 Mn 0.04 O δ A graph showing the impact of cathode active materials on capacity and efficiency;
[0108] Figure 14 To represent the effect of molar ratio (denoted by α) and Mn content (denoted by x) on Li according to an exemplary embodiment. α Co 0.96 Mn 0.04 O δ A graph showing the influence of the c-axis lattice parameter on the data;
[0109] Figure 15 To represent Li according to the exemplary implementation scheme α Co 0.96 Mn 0.04 A graph showing the variation of the c-axis lattice parameter of O2 with molar ratio;
[0110] Figure 16 A set of scanning electron microscope images of powders prepared at 900°C, 1000°C, 1050°C and 1100°C according to exemplary embodiments;
[0111] Figure 17 A set of scanning electron microscope micrographs based on an exemplary embodiment shows the effects of temperature and molar ratio α on particle morphology;
[0112] Figure 18 To represent the mixing ratio containing Li according to the exemplary implementation scheme α Co 0.96 Mn 0.04 O δ A graph showing the impact of cathode active materials on capacity and efficiency;
[0113] Figure 19 To include Li according to the exemplary implementation scheme α Co 1-x Mn x O δ Furthermore, a set of scanning electron microscope images of the cathode active material prepared by the co-precipitation method;
[0114] Figure 20 To prepare according to the exemplary embodiment by the coprecipitation method and containing Li α Co0.96 Mn 0.04 O δ Li α Co 0.90 Mn 0.10 O δ and Li α Co 0.84 Mn 0.16 O δ X-ray diffraction patterns of cathode active materials (with different α values);
[0115] Figure 21 To prepare according to the exemplary embodiment by the coprecipitation method and containing Li α Co 0.78 Mn 0.22 O δ and Li α Co 0.72 Mn 0.28 O δ X-ray diffraction patterns of cathode active materials (with different α values);
[0116] Figure 22 To include Li according to the exemplary implementation scheme α Co 1-x Mn x O δ Furthermore, a set of scanning electron microscope images of the cathode active material prepared according to the sol-gel method;
[0117] Figure 23 The preparation according to the sol-gel method according to the exemplary embodiment and containing Li 1.131 Co 0.90 Mn 0.10 O2, Li 1.198 Co 0.84 Mn 0.16 O2, Li 1.241 Co 0.78 Mn 0.22 O2 and Li 1.301 Co 0.72 Mn 0.28 X-ray diffraction pattern of the cathode active material of O2;
[0118] Figure 24 According to the exemplary embodiments, the components include LiCoO2 and Li 1.05 Co 0.96 Mn 0.04 O2, Li 1.05 Co 0.93 Mn 0.07 O2, Li 1.110 Co 0.90 Mn 0.10 O2 and Li1.19 Co 0.72 Mn 0.28 Differential capacity curve of the cathode active material of O2;
[0119] Figure 25 To include Li according to the exemplary implementation scheme 1.05 Co 0.96 Mn 0.04 O2, Li 1.05 Co 0.93 Mn 0.07 O2, Li 1.110 Co 0.90 Mn 0.10 O2 and Li 1.19 Co 0.72 Mn 0.28 Voltage characteristic curve of the cathode active material of O2;
[0120] Figure 26 According to the exemplary embodiment, with the substitution of Mn and Co 1-x Mn x The ratio of [Li] / [Co] to lithium 1-x Mn x [And the contour plot of the changing discharge energy density;]
[0121] Figure 27 According to the exemplary embodiment, with the substitution of Mn and Co 1-x Mn x The ratio of [Li] / [Co] to lithium 1-x Mn x [And the contour map of the changing energy retention rate;]
[0122] Figure 28 To include Li according to the exemplary implementation scheme α Co 0.99-y Al y Mn 0.01 O δ Li α Co 0.98-y Al y Mn 0.02 O δ Li α Co 0.97-y Al y Mn 0.03 O δ and Li α Co 0.96-y Al y Mn 0.04 O δ The differential capacity curve of the cathode active material;
[0123] Figure 29 To include Li according to the exemplary implementation scheme 0.977 Co 0.97 Al y Mn 0.03 O δ Li 0.992 Co 0.97 Al y Mn 0.03 O δ Li 1.003 Co 0.97 Al y Mn 0.03 O δ and Li 1.014 Co 0.97 Al y Mn 0.03 O δ The differential capacity curve of the cathode active material;
[0124] Figure 30 To include Li according to the exemplary implementation scheme 0.992 Co 0.97 Mn 0.03 O δ Li 1.003 Co 0.97 Mn 0.03 O δ and Li 1.014 Co 0.97 Mn 0.03 O δ The curve of discharge energy versus cycle count for the cathode active material;
[0125] Figure 31 To include Li according to the exemplary implementation scheme α Co 0.98-y Al y Mn 0.02 O δ Li α Co 0.97-y Al y Mn 0.03 O δ and Li α Co 0.96-y Al y Mn 0.04 O δ The curve of discharge energy versus cycle count for the cathode active material;
[0126] Figure 32 For Li according to the exemplary implementation scheme α Co 0.97 Mn 0.03 O δand Li α Co 0.97 Mn 0.03 O δ A curve of the nuclear magnetic resonance pattern;
[0127] Figure 33 To include Li according to the exemplary implementation scheme 1.01 Co 0.97-y Al y Mn 0.03 O δ The discharge energy versus cycle count curves of cathode active materials (with 0.077, 0.159, and 0.760 wt% Al2O3 added);
[0128] Figure 34A For the preparation of a Li-containing precursor by calcination according to an exemplary embodiment α Co 1-x-y Al y Mn x O δ Scanning electron microscope image of cathode active material particles;
[0129] Figure 34B For the exemplary implementation scheme Figure 34B Scanning electron microscope images of cathode active materials, but the precursors were calcined at higher sintering temperatures;
[0130] Figure 35A The product prepared from a precursor calcined at 1050°C according to an exemplary embodiment and containing Li α Co 1-x- y Al y Mn x O δ The particle size distribution of the cathode active material;
[0131] Figure 35B For the preparation of a precursor containing Li by calcination at 1085°C according to an exemplary embodiment α Co 1-x-y Al y Mn x O δ The particle size distribution of the cathode active material;
[0132] Figure 36 To include Li according to the exemplary implementation scheme 1.01 Co 1-x-y Al y Mn x O δ The curves showing the change in surface area and energy retention rate of the cathode active material versus calcination temperature;
[0133] Figure 37 To include Li according to the exemplary implementation scheme 1.01 Co 1-x-y Al y Mn x O δ The curves of initial discharge capacity and coulombic efficiency of the cathode active material versus calcination temperature;
[0134] Figure 38 According to the exemplary embodiments, the components include LiCoO2 and Li α Co 0.99 Mn 0.01 O δ Li α Co 0.98 Mn 0.02 O δ Li α Co 0.97 Mn 0.03 O δ Li α Co 0.96 Mn 0.04 O δ and Li α Co 0.93 Mn 0.07 O δ The curve of heat flow versus calcination temperature of the cathode active material;
[0135] Figure 39 According to the exemplary embodiments, the components include LiCoO2 and Li α Co 0.98 Mn 0.02 O δ Li α Co 0.97 Mn 0.03 O δ Li α Co 0.96 Mn 0.04 O δ and Li α Co 0.93 Mn 0.07 O δ A curve showing the relationship between the C-axis lattice parameters of the cathode active material and the lithium content;
[0136] Figure 40 According to the exemplary embodiments, the components include LiCoO2 and Li α Co 0.96 Mn 0.04 O δ and Li α Co 0.93 Mn 0.07O δ The Raman spectrum curve of the cathode active material;
[0137] Figure 41 To include Li according to the exemplary implementation scheme α Co 0.96 Mn 0.04 O δ and Li α Co 0.93 Mn 0.07 O δ The discharge capacity versus lithium content curve of the cathode active material after 52 cycles.
[0138] Figure 42 To include Li according to the exemplary implementation scheme 1.025 Co 0.96-y Al y Mn 0.04 O δ and Li 1.00 Co 0.93- y Al y Mn 0.07 O δ The differential capacity curve of the cathode active material; and
[0139] Figure 43 To include Li according to the exemplary implementation scheme α Co 0.96 Mn 0.04 O δ The graph shows the data of the first cycle charge capacity, first cycle discharge capacity, and first cycle coulombic efficiency of the cathode active material in relation to lithium content. Detailed Implementation
[0140] The following description is provided to enable any person skilled in the art to develop and use embodiments, and is provided in the context of a particular application and its requirements. Various modifications to the embodiments disclosed herein will be apparent to those skilled in the art, and the general principles defined herein can be applied to other embodiments and applications without departing from the spirit and scope of this disclosure. It should be understood that the following description is not intended to limit the embodiments to a single preferred embodiment. Rather, it is intended to cover alternative forms, modifications, and equivalents that may be included within the spirit and scope of the embodiments defined by the appended claims. Therefore, this disclosure is not limited to the embodiments shown, but is to be accorded the broadest scope according to the principles and features disclosed herein.
[0141] As used herein, unless otherwise specified, all compositions used for cathode active materials represent the composition of the prepared material (i.e., the “raw” material). These compositions have not been exposed to additional processes, such as delithiation and lithiation during lithium-ion battery charging and discharging, respectively.
[0142] Lithium cobalt oxides can be used in cathode active materials for commercial lithium-ion batteries. These compounds typically contain lithium cobalt oxide or its derivatives. The performance of such cathode active materials can be enhanced by increasing their capacity, operating voltage, and gravimetric electrode density.
[0143] The morphology of particles can also affect the performance of cathode active materials. Particles can include primary particles and secondary particles. The particle size distribution, shape, and porosity of primary and secondary particles can affect the density of lithium cobalt oxide electrodes. Secondary particles consist of agglomerates of smaller primary particles (often referred to as grains). The shape and density of secondary particles can be controlled.
[0144] Compounds and particles that provide increased capacity, operating voltage, and gravimetric electrode density can be used to improve battery performance. The disclosure herein addresses these and other needs.
[0145] Figure 1 A top view of a battery cell 100 according to one embodiment is shown. The battery cell 100 may correspond to a lithium-ion or lithium-polymer battery cell for powering devices used in consumer, medical, aerospace, defense, and / or transportation applications. The battery cell 100 includes a stack 102 comprising multiple layers, said multiple layers including a cathode with a cathode active coating, a separator, and an anode with an anode active coating. More specifically, the stack 102 may include a cathode active material strip (e.g., aluminum foil coated with a lithium compound) and an anode active material strip (e.g., copper foil coated with carbon). The stack 102 also includes a separator material strip (e.g., a conductive polymer electrolyte) disposed between the cathode active material strip and the anode active material strip. The cathode, anode, and separator layers may remain flat in a planar configuration or may be wound into a wound configuration (e.g., a "gel roll").
[0146] The battery cells can be encapsulated in a flexible bag. (Back) Figure 1 During the assembly of the battery cell 100, the stack 102 is encapsulated in a flexible bag. The stack 102 can be planar or rolled up, but other configurations are also possible. The flexible bag is formed by folding a flexible sheet along fold line 112. For example, the flexible sheet can be made of aluminum with a polymer film (e.g., polypropylene). After folding the flexible sheet, the flexible sheet can be sealed, for example, by applying heat along the side seal 110 and along the platform seal 108. The thickness of the flexible bag can be less than 120 micrometers to improve the encapsulation efficiency of the battery cell 100, the density of the battery cell 100, or both.
[0147] The stack 102 also includes a set of conductive leads 106 coupled to the cathode and anode. The conductive leads 106 may extend through a seal in the bag (e.g., a seal formed using sealing tape 104) to provide terminals for the battery cell 100. The conductive leads 106 can then be used to electrically couple the battery cell 100 to one or more other battery cells to form a battery pack.
[0148] Batteries can be combined in battery packs of any configuration. For example, a battery pack can be formed by coupling battery cells in series, parallel, or series-parallel configurations. Such coupled cells can be encapsulated in a rigid housing to complete the battery pack, or can be embedded in the casing of portable electronic devices such as laptops, tablets, mobile phones, personal digital assistants (PDAs), digital cameras, and / or portable media players.
[0149] Figure 2 A battery cell (e.g., according to an embodiment disclosed in the present invention) is shown. Figure 1 The image shows a side view of a set of layers in a battery cell 100. This set of layers may include a cathode current collector 202, a cathode active coating 204, a separator 206, an anode active coating 208, and an anode current collector 210. The cathode current collector 202 and the cathode active coating 204 may form the cathode of the battery cell, and the anode current collector 210 and the anode active coating 208 may form the anode of the battery cell. To form the battery cell, the set of layers may be stacked in a planar configuration or stacked and then wound into a wound configuration.
[0150] As described above, the cathode current collector 202 may be an aluminum foil, the cathode active coating 204 may be a lithium compound, the anode current collector 210 may be a copper foil, the anode active coating 208 may be carbon, and the separator 206 may contain a conductive polymer electrolyte.
[0151] It should be understood that the cathode active materials described herein can be used in conjunction with any battery cell or component thereof known in the art. For example, in addition to wound battery cells, layers can be stacked and / or used to form other types of battery cell structures, such as dual-cell structures. All such battery cell structures are known in the art.
[0152] This invention discloses a surface-modified and structurally stable lithium cobalt oxide material. This material can be used as a cathode active material in lithium-ion batteries.
[0153] In various respects, transition metal oxides are variations of lithium cobalt oxides. In one aspect, this disclosure relates to compounds of formula (I):
[0154] Li α MO δ (I)
[0155] Where M is Co, Mn, Ni, or any combination thereof, 0.95 ≤ α ≤ 2 and 2 ≤ δ ≤ 3. In some variations, 1 ≤ α ≤ 2. In some variations, 1.20 ≤ α. In some variations, 1.40 ≤ α. In some variations, 1.60 ≤ α. In some variations, 1.80 ≤ α. In some variations, α ≤ 1.8. In some variations, α ≤ 1.6. In some variations, α ≤ 1.4. In some variations, α ≤ 1.2. In some variations, α ≤ 1.8. Furthermore, in some variations, 2.2 ≤ δ. In some variations, 2.4 ≤ δ. In some variations, 2.6 ≤ δ. In some variations, 2.8 ≤ δ. In some variations, δ ≤ 2.8. In some variations, δ ≤ 2.6. In some variations, δ ≤ 2.4. In some variations, δ ≤ 2.2. It should be understood that the boundaries of α and δ can be combined in any of the above variations.
[0156] In all respects, this disclosure relates to compounds of formula (IIa):
[0157] (x)[Li2M 1 O3]·(1-x)[LiM 2 O2] (IIa)
[0158] Where M 1 M is one or more cations with an average oxidation state of 4+ (i.e., tetravalent). 2 M is one or more cations with an average oxidation state of 3+ (i.e., trivalent), and 0 ≤ x ≤ 1. In some variants, M 1 Selected from Ti, Mn, Zr, Mo, Ru, and combinations thereof. In certain variations, M... 1 For Mn. In some variations, M 2 Selected from B, Na, Mg, Ti, Ca, V, Cr, Mn, Fe, Co, Ni, Cu, Zn, Al, Sc, Y, Ga, Zr, Ru, Mo, and combinations thereof. In some variations, M... 2 Selected from Mg, Ca, V, Cr, Mn, Fe, Co, Ni, Cu, Zn, Al, Sc, Y, Ga, Zr, and combinations thereof. In certain variations, M... 2 For Co.
[0159] It should be understood that in the representation of excess lithium transition metal oxides, M = [M 2 ] 1-x [M 1 ] xα = 1 + x, and δ = 2 + x. In some variations, α ≤ 1.2. In some variations, α ≤ 1.4. In some variations, α ≤ 1.6. In some variations, α ≤ 1.8. In some variations, 1.2 ≤ α. In some variations, 1.4 ≤ α. In some variations, 1.6 ≤ α. In some variations, 1.8 ≤ α. It should be understood that the boundaries of x can be combined with any of the variations above. For the embodiments disclosed herein, cobalt is the primary transition metal component, which allows for high voltage and high volumetric energy density of the cathode active material used in lithium-ion batteries.
[0160] In all respects, this disclosure relates to compounds of formula (IIb):
[0161] (x)[Li2M 1 O3]·(1-x)[Li 1-y M 2 O2] (IIb)
[0162] Where M 1 M is one or more cations with an average oxidation state of 4+ (i.e., tetravalent). 2 It can be one or more cations, 0 ≤ x ≤ 1, and 0 ≤ y ≤ 1. In some variations, M 1 Selected from Ti, Mn, Zr, Mo, Ru, and combinations thereof. In certain variations, M... 1 For Mn. In some variations, M 2 Selected from B, Na, Mg, Ti, Ca, V, Cr, Mn, Fe, Co, Ni, Cu, Zn, Al, Sc, Y, Ga, Zr, Ru, Mo, and combinations thereof. In some variations, M... 2 Selected from Mg, Ti, Ca, V, Cr, Mn, Fe, Co, Ni, Cu, Zn, Al, Sc, Y, Ga, Zr, and combinations thereof. In some variations, M... 2 Selected from Mg, Ca, V, Cr, Mn, Fe, Co, Ni, Cu, Zn, Al, Sc, Y, Ga, Zr, and combinations thereof. In certain variations, M... 2 For Co and Mn.
[0163] It should be understood that in the representation of excess lithium transition metal oxides, M = [M 2 ] 1-x [M 1 ] x, α=1+x-y+xy, and δ=2+x. In some variants, α≤0.98. In some variants, α≤1.0. In some variants, α≤1.1. In some variants, α≤1.2. In some variants, 0.95≤α. In some variants, 1.3≤α. In some variants, 1.6≤α. In some variants, 1.8≤α. It should be understood that the boundaries of α can be combined in any of the variants as described above. For the embodiments disclosed herein, cobalt is the main transition metal component, which allows high voltage and high volumetric energy density for cathode active materials employed in lithium-ion batteries.
[0164] In some variants, the present disclosure relates to a compound represented by formula (III):
[0165] Li α Co 1-x M x Al γ O δ (III)
[0166] wherein M is selected from B, Na, Mn, Ni, Mg, Ti, Ca, V, Cr, Fe, Cu, Zn, Al, Sc, Y, Ga, Zr, Mo, Ru, one combination thereof or any combination thereof; 0.95≤α≤1.10; 0<x<0.50; 0≤γ≤0.05; and 1.95≤δ≤2.60. In some variants, M is Mn, Ni or any combination thereof. In some variants, M is Mn, Ni or a combination thereof, 0.95≤α≤1.10, 0<x<0.50, 0≤γ≤0.05, and 1.95≤δ≤2.60. In some variants, 0.01≤γ≤0.03. In some variants, 0.001≤γ≤0.005. In some variants, 0.002≤γ≤0.004. In some variants, γ is 0.003. In some variants, 0.02≤γ≤0.03. In such variants of formula (III) where γ≠0 (i.e., aluminum is present), the aluminum distribution within the particles may be uniform or may be biased to be adjacent to the surface of the particles. Other aluminum distributions are also possible. In some variants, Al is at least 500 ppm. In some variants, Al is at least 750 ppm. In some variants, Al is at least 900 ppm. In some variants, Al is less than or equal to 2000 ppm. In some variants, Al is less than or equal to 1500 ppm. In some variants, Al is less than or equal to 1250 ppm. In some variants, Al is about 1000 ppm.
[0167] In another variation of equation (III), 1.02 ≤ α ≤ 1.05 and 0.02 ≤ x ≤ 0.05. In another variation of equation (III), 1.03 ≤ α ≤ 1.05 and x = 0.04. It should be understood that the components described above can be any combination.
[0168] The various compounds of formulas (I), (IIa), (IIb) and (III) may contain Mn 4+ We do not wish to be limited by any theory or mode of action; the incorporated Mn... 4+ This can improve the stability of oxides under high-voltage charging (e.g., 4.5V) and also help maintain stability during the transition through the 4.1 to 4.3V region (i.e., during charging and discharging). Its crystal structure (i.e., α-NaFeO2 structure).
[0169] In some embodiments, this disclosure relates to powders comprising particles. In some aspects, the particles may comprise compounds of formula (III) and novel formulas. In some variations, the particles comprise a core containing a compound of formula (I), (IIa), (IIb), or (III) and a coating disposed on at least a portion of the core. In other variations, the particles comprise a core containing a compound of formula (III) and a coating disposed on at least a portion of the core.
[0170] It should be understood that powders can be used as part or all of the cathode active material. The particles described herein can be used as cathode active materials in batteries. Such cathode active materials can withstand conditions equal to or higher than conventional materials (i.e., relative to Li / Li). + The redox pair (voltage) has no capacity decay. Capacity decay reduces battery performance and may be caused by structural instability of the cathode active material, side reactions of the electrolyte at high voltage, surface instability, dissolution of the cathode active material in the electrolyte, or some combination thereof.
[0171] In the case of a particle containing a compound of formula (III) and a variant containing aluminum, aluminum can be referred to as a dopant. Such aluminum dopants can be uniformly distributed throughout the particle or located along the surface of the particle.
[0172] In other variations, the particles comprise a core and a coating. The coating may be an oxide material, a fluoride material, or a combination thereof. In some variations, the coating may be a layer of material in contact with the surface of the core or a reactive layer formed along the surface of the core. The coating may comprise oxide materials (e.g., ZrO2, Al2O3, etc.), fluoride materials (e.g., AlF3), or combinations thereof (e.g., AlO2, Al2O3, etc.). x F yIn some embodiments, the oxide material comprises at least one element selected from Al, Co, Li, Zr, Mg, Ti, Zn, Mn, B, Si, Ga, and Bi. In these embodiments, the oxide material may comprise oxyanions, such as phosphate (e.g., AlPO4, Co3(PO4)2, LiCoPO4, etc.). In some embodiments, the fluoride material comprises at least one element selected from Al, Co, Mn, Ni, Li, Ca, Zr, Mg, Ti, and Na. The coating may comprise one or more compositions selected from AlF3, Al2O3, AlPO4, Co3(PO4)2, LiCoPO4, and ZrO2.
[0173] The coating can be any amount known in the art. In some variations, the amount of coating may be less than or equal to 7% by weight of the total particles. In some variations, the amount of coating may be less than or equal to 5% by weight of the total particles. In some variations, the amount of coating may be less than or equal to 0.8% by weight of the total particles. In some variations, the amount of coating may be less than or equal to 0.6% by weight of the total particles. In some variations, the amount of coating may be less than or equal to 0.4% by weight of the total particles. In some variations, the amount of coating may be less than or equal to 0.3% by weight of the total particles. In some variations, the amount of coating may be less than or equal to 0.2% by weight of the total particles. In some variations, the amount of coating may be less than or equal to 0.1% by weight of the total particles. In each aspect, the amount may be selected such that the capacity of the cathode active material is not negatively affected.
[0174] The coating may comprise multiple layers of coating material. The coating may also be a continuous or discontinuous coating. Non-limiting examples of discontinuous coatings include coatings with voids or cracks, and coatings formed by particles with gaps between them. Other types of discontinuous coatings are also possible.
[0175] Powders containing the particles described herein can be used as cathode active materials in lithium-ion batteries. Such cathode active materials can withstand conditions equal to or higher than conventional materials (i.e., relative to Li / Li). + The redox pair (voltage) has no capacity decay. Capacity decay reduces battery performance and may be caused by structural instability of the cathode active material, side reactions of the electrolyte at high voltage, surface instability, dissolution of the cathode active material in the electrolyte, or some combination thereof.
[0176] In various respects, the compounds and / or particles described herein, when incorporated into batteries as cathode active materials, enable lithium-ion batteries to be charged at high voltages without capacity decay. Where it is undesirable to be limited by a specific mechanism or mode of action, the compounds can hinder or delay structural deviations from the α-NaFeO2 crystal structure during charging to higher voltages.
[0177] In various aspects, the compounds described herein, when incorporated into batteries as cathode active materials, enable lithium-ion batteries to have voltages greater than 4.2V without capacity decay. In other aspects, such batteries have voltages greater than 4.3V. In various aspects, lithium cobalt oxide materials relate to voltages greater than 4.4V. In various aspects, lithium cobalt oxide materials relate to voltages greater than 4.5V.
[0178] Batteries having cathode active materials comprising the particles disclosed in this invention can exhibit improved battery performance at high voltages. For example, the particles provide increased battery capacity during cycling at high voltages (e.g., 4.5V). In some variations, the battery degradation rate is less than 0.7 mAh / g / cycle at a charging potential of 4.5V. In some variations, the battery degradation rate is less than 0.6 mAh / g / cycle at a charging potential of 4.5V. In some variations, the battery degradation rate is less than 0.5 mAh / g / cycle at a charging potential of 4.5V.
[0179] In some other variations, batteries comprising cathode active materials containing the particles disclosed in this invention lose a smaller amount of energy per unit mass per cycle. In some embodiments, such batteries lose less than 4 Wh / kg per cycle when operating at a potential of 4.5 V. This disclosure also relates to methods for preparing the compounds and particles disclosed in this invention.
[0180] In embodiments of the compound containing particles or a core (VI), aluminum can be introduced via surface modification methods. For example, but not limited to, particles can be coated with an aluminum-containing coating and subsequently heated. Thermal energy can promote a reaction between the particles and the coating, thereby injecting aluminum into the core (e.g., doping). In another non-limiting example, the particles can be exposed to a solution containing aluminum. A chemical reaction between the particles and the solution can form a surface reaction layer containing aluminum. The particles can then be heated (e.g., to diffuse aluminum from the surface reaction layer into the particles, to convert the surface reaction layer into a coating, etc.). In another non-limiting example, the particles can be contacted with aluminum-containing particles, for example, during milling. Mechanical energy generates compressive forces, shear forces, or combinations thereof, to fuse aluminum particles into the particles (e.g., to bind Al₂O₃ nanoparticles into the particles). These surface modification methods allow the core to achieve an aluminum content between 0 < γ ≤ 0.03. Other surface modification methods are also possible.
[0181] In various implementations, the performance of batteries containing compounds and / or powders can increase battery capacity and / or reduce the available power loss of a fully charged battery over time.
[0182] This disclosure also relates to methods for modifying particulate surfaces by wet or dry processing.
[0183] In another aspect, this disclosure relates to a method for preparing particles. A precursor solution comprising a first amount of a precursor dissolved in a solvent is prepared. The powder comprises a compound conforming to formula (I), (IIa), (IIb), or (III). The precursor solution is added to the powder to form a wet-impregnated powder. The wet-impregnated powder is heated to a high temperature.
[0184] On the other hand, a first precursor is dissolved in a first portion of a solvent to form a first solution. The first solution is added to a powder to form a partially wet-impregnated powder. A second precursor is dissolved in a second portion of a solvent to form a second solution. The second solution is added to the partially wet-impregnated powder to prepare a wet-impregnated powder. The wet-impregnated powder is then heated at a high temperature.
[0185] Wet impregnation involves adding a solvent to powder particles until the particles exhibit a wet consistency (e.g., similar to a paste). In various aspects, the amount of solvent can be selected such that when a precursor solution is added to the powder, the resulting wet-impregnated powder exhibits a wet consistency. The method also includes heating the wet-impregnated powder at a high temperature. It should be understood that the amount of solvent can be determined by selecting a known amount of powder and gradually adding solvent until all particles of the powder appear wet but not flowing (i.e., exhibiting a wet consistency). When using this method, the solvent-to-powder ratio (e.g., grams of solvent per gram of powder) can be scaled as needed to accommodate different amounts of powder. The concentration of at least one precursor can then be selected to apply the desired amount of material to the surface of the particles. Representative variations of this method are described with reference to Examples 1, 3, 4, 5, and 6.
[0186] In some embodiments, the powder subjected to heated wet impregnation comprises powder subjected to dried wet impregnation. In some embodiments, at least one precursor comprises aluminum (e.g., see Example 1).
[0187] In some embodiments, preparing the precursor solution includes dissolving a first precursor in a first portion of a solvent to form a first solution, and dissolving a second precursor in a second portion of the solvent to form a second solution. The total amount of the first and second portions of the solvent may correspond to the amount of solvent. In these embodiments, preparing the precursor solution further includes mixing the first and second solutions to form the precursor solution. In some cases, the first precursor comprises aluminum, and the second precursor comprises a phosphate (e.g., see Example 3). In other cases, the first precursor comprises cobalt, and the second precursor comprises a phosphate (e.g., see Example 4). In still other cases, the first precursor comprises aluminum, and the second precursor comprises lithium (e.g., see Example 5).
[0188] In some embodiments, preparing the precursor solution includes dissolving a first precursor in a first portion of a solvent to form a first solution, dissolving a second precursor in a second portion of the solvent to form a second solution, and dissolving a third precursor in a third portion of the solvent to form a third solution. The first portion, the second portion, and the third portion of the solvent total the amount of solvent. In such embodiments, preparing the precursor solution further includes mixing the first, second, and third solutions to form the precursor solution.
[0189] In some embodiments, at least one of the first precursor, the second precursor, and the third precursor comprises lithium. In some embodiments, the first precursor comprises cobalt, the second precursor comprises lithium, and the third precursor comprises a phosphate (e.g., see Example 6).
[0190] In some embodiments, adding the first solution to the powder includes drying the wet-impregnated powder. In some embodiments, heating the wet-impregnated powder includes drying the wet-impregnated powder. In some embodiments, the first precursor comprises aluminum, and the second precursor comprises fluorine (e.g., see Example 2).
[0191] According to one exemplary embodiment, a method for modifying the surface of particles includes stirring a particle suspension. The particles comprise a compound of formula (III). The method also involves adding one or more precursors to the particle suspension while stirring. In some embodiments, the method further includes filtering the particles after adding the precursor solution. Representative variations of the method are described with reference to Examples 7 through 9.
[0192] In some embodiments, the method includes filtering the particles after adding at least one precursor and heating the filtered particles to a high temperature. In some embodiments, the precursor solution may contain aluminum or cobalt (e.g., see Example 8). Non-limiting examples of metal precursors include: aluminum precursors, such as Al(NO3)3; and cobalt precursors, such as Co(NO3)3.
[0193] According to an exemplary embodiment, a method for modifying the surface of particles in a powder includes blending nanocrystalline material particles with powder particles. The powder particles may contain compounds conforming to formulas (I), (IIa), or (III) as described herein. The particles may be mixed with and simultaneously blended with the nanocrystalline material, and / or subjected to compressive forces, shear forces, or combinations thereof. Such forces can induce the nanocrystalline material particles to bind to the surface of the powder particles. The nanocrystalline material particles and powder particles may be blended in a certain ratio such that the nanocrystalline material particles form a predetermined amount of coating on the powder particles. Representative variations of this method are described with reference to Examples 10 to 12. In some embodiments, the nanocrystalline material particles may contain alumina, aluminum fluoride, or combinations thereof.
[0194] In some variations, the present disclosure relates to a compound represented by Formula (IV):
[0195] Li α Co 1-x Mn x O δ (IV)
[0196] wherein 0.95≤α≤1.10, 0≤x≤0.10, and 1.90≤δ≤2.20. In some variations, 0.98≤α≤1.01. In some variations of Formula (IV), 0.98≤α≤1.01 and x=0.03. In some variations of Formula (IV), 1.00≤α≤1.05. In some variations, 0<x≤0.10. In further variations, the present disclosure relates to the compound represented by Formula (IV), wherein 0.95≤α≤1.05 and 0.02≤x≤0.05. In another aspect, the present disclosure relates to the compound represented by Formula (IV), wherein 0.95≤α≤1.05 and x=0.04. In some variations, x=0.03. In further variations of Formula (IV), 1.01≤α≤1.05 and 0.02≤x≤0.05. In further variations of Formula (IV), 1.01≤α≤1.05 and x=0.04. In some variations of Formula (IV), 1.00<α≤1.10. In other variations of Formula (IV), 1.00<α≤1.05. In another aspect, the present disclosure relates to the compound represented by Formula (IV), wherein 0.98≤α≤1.01, x=0.03, and δ=2.
[0197] It should be understood that α represents the molar ratio of lithium content to total transition metal content (i.e., the total content of Co and Mn). In various aspects, increasing the lithium content may increase capacity, improve stability, increase the weight density of particles comprising the compound, increase particle density, and / or increase the particle strength of the cathode active material. In various aspects, decreasing the lithium content may increase capacity, improve stability, increase the weight density of particles comprising the compound, increase particle density, and / or increase the particle strength of the cathode active material.
[0198] In some variations, the compound of Formula (IV) may be expressed as a solid solution of two phases, i.e., a solid solution of Li₂MnO₃ and LiCoO₂. In these variations, the compound may be described according to Formula (Va):
[0199] (x)[Li₂MnO₃]·(1-x)[LiCoO₂] (Va)
[0200] wherein Mn is a cation with an average oxidation state of 4+ (i.e., tetravalent), and Co is a cation with an average oxidation state of 3+ (i.e., trivalent). A more compact notation of Formula (Va) is shown below:
[0201] Li 1+x Co 1-x Mn x O 2+x (VI)
[0202] In formula (VI), x describes that both Mn and Co are included. Due to the different valences existing between Mn and Co, the inclusion of Mn in this way may affect the lithium content and oxygen content of the compound.
[0203] In formula (IV), the composition of "x" may be 0≤x≤0.10. In some variants, 0<x≤0.10. In such variants, the lithium content in formula (VI) may be 1 to 1.10, and the oxygen content may be 2 to 2.10. However, the compounds disclosed herein have lithium content and oxygen content that can vary independently of x. For example, but not limited to, the lithium content and the oxygen content may differ in terms of stoichiometric values due to synthetic conditions intentionally selected by those skilled in the art. Therefore, the subscripts in formula (V) and formula (VI) are not intended to limit formula (IV), that is, α is not necessarily equal to 1+x, and δ is not necessarily equal to 2+x. It should be understood that the lithium content and oxygen content of the compound represented by formula (IV) may be sub-stoichiometric or super-stoichiometric relative to the stoichiometric values of formula (VI).
[0204] In some variants, the compound of formula (IV) may be represented as a solid solution of two phases, that is, a solid solution of Li₂MnO₃ and LiCoO₂. In these variants, the compound may be described according to formula (Vb):
[0205] (x)[Li₂MnO₃]·(1-x)[Li (1-y) Co (1-y) Mn y O₂] (Vb)
[0206] wherein Mn is a cation with an average oxidation state of 4+ (i.e., tetravalent), and Co is a cation with an average oxidation state of 3+ (i.e., trivalent).
[0207] The present disclosure also relates to powders comprising the compounds described herein. In various aspects, the present disclosure relates to a powder comprising Li-containing α Co 1-x Mn x O δparticles, wherein 0.95≤α≤1.10, 0≤x≤0.10, and 1.90≤δ≤2.20. In some variants, 0<y≤0.10. The powder can be used as part or all of a cathode active material (i.e., the cathode active material comprises the powder). In some embodiments, 0.98≤α≤1.01 and x=0.03. In some embodiments, 1.00≤α≤1.05. In further embodiments, 1.01≤α≤1.05 and 0.02≤x≤0.05. In further embodiments, 1.01≤α≤1.05 and x=0.04. In some embodiments, 1.00<α≤1.10. In other embodiments, 1.00<α≤1.05.
[0208] In some variants, the compound of formula (IV) can be represented as a solid solution of two phases, namely a solid solution of Li₂MnO₃ and LiCoO₂. In these variants, the compound can be described according to formula (Va) or formula (Vb), wherein Mn is a cation having an average oxidation state of 4+ (i.e., tetravalent), and Co is a cation having an average oxidation state of 3+ (i.e., trivalent).
[0209] Alternatively, a more compact notation is represented as formula (Vc):
[0210] Li 1+x-y-xy Co (1-x)*(1-y) Mn (x+y-x*y) O 2+x (Vc)
[0211] In formula (Vc), x can describe both Mn and Co. Without wishing to be bound by a particular mechanism or mode of action, due to the different valences existing between Mn and Co, the inclusion of Mn may affect the lithium content and oxygen content of the compound.
[0212] In formula (Vc), the combination of "x" and "y" is at least zero and less than or equal to 0.10. In some variants, the combination of "x" and "y" can be greater than zero and less than or equal to 0.10. In such variants, for other formulas, the lithium content can be any of the ranges described herein. In some variants, lithium can be from 0.9 to 1.10. In some variants, the oxygen content can be from 2 to 2.10. It should be understood that with respect to all formulas presented herein, the compounds disclosed herein have a lithium content and an oxygen content that can vary independently of x and y.
[0213] The compounds and powders can be cathode active materials for lithium-ion batteries, as described herein. These cathode active materials assist in energy storage by releasing and storing lithium ions during charging and discharging of the lithium-ion battery, respectively.
[0214] To avoid being limited to a specific mechanism or mode of action, the properties of powders can provide improved battery performance when used as cathode active materials. Powders containing the compounds described herein have increased tap density compared to previously known compounds. Batteries containing these powders as cathode active materials exhibit increased volumetric energy density.
[0215] In some cases, batteries with this type of cathode active material have a specific capacity greater than 130 mAh / g. In some cases, the specific capacity is greater than 140 mAh / g. In some cases, the specific capacity is greater than 150 mAh / g. In some cases, the specific capacity is greater than 160 mAh / g. In some cases, the specific capacity is greater than 170 mAh / g.
[0216] Increasing the initial lithium content in the cathode active material (e.g., the prepared lithium content) can increase the volumetric energy density and / or cycle life.
[0217] Cathode active materials can exhibit high tap density and / or improved particle strength. In some cases, cathode active materials can exhibit a tap density equal to or greater than 2.1 g / cm³. 3 The tap density. In some cases, the cathode active material can exhibit a tap density equal to or greater than 2.2 g / cm³. 3 The tap density. In some cases, the cathode active material can exhibit a tap density equal to or greater than 2.3 g / cm³. 3 The tap density. In some cases, the cathode active material can exhibit a tap density greater than or equal to 2.4 g / cm³. 3 The tap density.
[0218] In some variations, this disclosure relates to cathode active materials for lithium-ion batteries, the cathode active material comprising Mn 4+ Lithium cobalt oxides are tetravalent metals. In these materials, trivalent Co ions (Co) are present. 3+ It can be used as a host to provide capacity. It is not desirable to be limited by any theory or mode of action when incorporating Mn. 4+ It can improve the stability of lithium cobalt oxide under high-voltage charging and also help maintain stability during the transition through the 4.1 to 4.6V region (i.e., during charging and discharging). Its crystal structure.
[0219] In some cases, the charging voltage may be equal to or greater than 4.4V. In some cases, the charging voltage may be equal to or greater than 4.5V. In some cases, the charging voltage may be equal to or greater than 4.6V.
[0220] The degree of Mn substitution can affect the amount of additional lithium required for the cathode active material. For example, but not limited to, a lithium cobalt oxide composition having 92% Co and 8% Mn can correspond to a lithium content of 6 mol% to 10 mol% excess units. However, in general, the lithium content range can vary based on the degree of manganese substitution and refer to... Figure 13 As shown, those skilled in the art can use empirical data to determine the lithium content range.
[0221] Figure 13 The molar ratio containing Li is presented according to the exemplary implementation scheme. α Co 0.96 Mn 0.04 O δ A graph showing the effect of the cathode active material's capacity (i.e., first cycle discharge capacity) and efficiency on (i.e., x = 0.04). The molar ratio indicated on the horizontal axis corresponds to α, which is the molar ratio of lithium content to total transition metal content (i.e., in...). Figure 13 The molar ratio is described as "Li / TM ratio" (as described in the text). To determine the molar ratio, inductively coupled plasma optical emission spectroscopy (ICP-OES) was used to chemically characterize the cathode active material, as is known to those skilled in the art. Capacity and efficiency are listed on the left and right sides of the vertical axis, respectively.
[0222] Further reference Figure 13 The first curve 300 represents the capacity as a function of the molar ratio fitted to a first set of data points 302. The second curve 304 represents the efficiency as a function of the molar ratio fitted to a second set of data points 306. For this specific composition (i.e., x = 0.04), the first curve 300 exhibits a maximum value corresponding to 0.98 ≤ α ≤ 1.05. However, it should be understood that the limitation of the range can be changed in response to changes in x, where x represents the amount of Mn in the cathode material. In general, those skilled in the art can change α and x to achieve the desired combination of capacity and efficiency.
[0223] In certain variants, the compounds described herein may allow for the storage of excess lithium. Figure 13 The study showed that adding lithium (i.e., 0.98 < α ≤ 1.05) increases the capacity of the cathode material relative to a unit (i.e., α = 1.00). This increased capacity allows those skilled in the art to match the specific (increased) capacity with the desired efficiency. Such an increased capacity is unintended. In various respects, additional lithium is generally expected to act as a contaminant in the cathode material, thereby degrading its performance. In fact, when excess lithium exceeds a threshold (e.g., in…),… Figure 13 When the value exceeds α (up to 1.05), both capacity and efficiency decrease.
[0224] In all respects, the compounds described herein provide increased capacity and stability of cathode active materials compared to known compounds. Figure 14 The molar ratio (denoted by α) and Mn content (denoted by x) of compound (IV) according to exemplary embodiments are presented for the effect of these ratios on the molar ratio (denoted by α) and Mn content (denoted by x). α Co 0.96 Mn 0.04 O δ A graph showing the effect of the c-axis lattice parameter on the data. Oxygen in the composition can correspond to δ = 2, but variations from this stoichiometry are also possible (i.e., within 1.90 ≤ δ ≤ 2.20). Data were generated using X-ray diffraction techniques, as is known to those skilled in the art. LiCoO2 The (003) peak of the diffraction pattern is characterized by shifts according to x and α. For a given x (e.g., 0.04 or 4 mol%), the c lattice shrinks as α increases (i.e., as α increases from 1.0062 to 1.0925). It is not desirable to be confined to any theory or mode of action, but it is believed that the presence of Mn... 4+ Excess lithium will move to Li α Co 0.96 Mn 0.04 O δ In the transition metal layer. This shift increases the lithium capacity and stability of the material.
[0225] Figure 15 The representation of Li according to the exemplary implementation scheme is presented. α Co 0.96 Mn 0.04 O δ A graph showing the c-axis lattice parameter as a function of molar ratio. (The molar ratio α is indicated on the x-axis as "ICP Li / TM"). Oxygen in the composition can correspond to δ = 2, but variations from this stoichiometry are also possible (i.e., within the range of 1.90 ≤ δ ≤ 2.20). To determine α, the cathode active material was chemically characterized using ICP-OES, as is known to those skilled in the art. The variation of the c-axis lattice parameter follows an S-shaped curve. The S-shaped curve tends to become an asymptote at the extreme values of α (i.e., ...). Figure 15 (The minimum and maximum values of α are shown).
[0226] This disclosure also relates to the preparation of Li-containing materials. α Co 1-x Mn x O δ A method for preparing a powder. The method includes the steps of mixing a lithium source with precursor particles to produce a reactant, and then heating the reactant to a high temperature.
[0227] The lithium ion cathode material precursor can be calcined to obtain the positive electrode material. However, it may be difficult to control the particle sintering process to produce high-density particles and simultaneously produce a high-capacity material. Due to its high evaporation rate at high temperatures, prior art procedures add variable amounts of additional lithium of up to 10% by weight.
[0228] The precursor particles comprise transition metal hydroxides containing Co and Mn. Non-limiting examples of lithium sources include lithium hydroxide (i.e., LiOH) and lithium carbonate (i.e., Li₂CO₃). However, other lithium sources are also possible.
[0229] The method further comprises heating the reactants to a temperature equal to or higher than 800°C. In these methods, 0≤x≤0.10 and 1.90≤δ≤2.20. In some variants, 0<x≤0.10. The ratio of the lithium source to the precursor particles is selected such that 0.95≤α≤1.10. Due to evaporation loss of lithium during heating, this ratio may be equal to or greater than the molar ratio α. In some embodiments, the temperature is between 800°C and 1200°C.
[0230] In some aspects, the heating temperature is from about 800°C to about 1000°C. In other aspects, the heating temperature is from about 1000°C to about 1100°C. In other aspects, the heating temperature is from about 1100°C to about 1200°C. In other aspects, the heating temperature is from about 900°C to about 1000°C. In other aspects, the heating temperature is from about 800°C to about 900°C. Without wishing to be bound by any mechanism or mode of action, temperatures within the aforementioned ranges allow the powder particles to exhibit sufficient weight density and strength suitable for lithium ion battery applications. These ranges also correspond to improved capacity and first cycle efficiency. Likewise, without wishing to be bound by any mechanism or mode of action, it should be understood that a high weight density allows the energy density of the cathode active material to be increased. Particle strength can improve effective handling during battery manufacturing and cycle stability during battery operation.
[0231] In various aspects, the molar ratio (i.e., α), temperature, and corresponding heating period can control the sintering and compaction of the particles. Figure 16 A set of scanning electron micrographs of powders prepared at 900°C, 1000°C, 1050°C, and 1100°C according to illustrative embodiments are presented. The temperature increases from left to right, and the magnification increases from top to bottom. The composition of the powder particles corresponds to α=1.04 and x=0.04. At 900°C and 1000°C, the powder particles retain the sheet-like structure of the precursor particles. The powders exhibit tap densities of 2.0 and 2.1 g / cm 3 respectively. However, at 1050°C and 1100°C, the morphology of the individual particles in the powder changes to smooth (i.e., smooth surface). This smooth morphology indicates partial melting during the process. The corresponding tap density increases to 2.3 to 2.4 g / cm 3These powders exhibit greater strength because the grains (i.e., primary particles) have grown and are better bonded together. Furthermore, the number of grains is reduced, and there are fewer grain boundaries present.
[0232] In these methods, the additional lithium content controls the degree of sintering of the precursor particles. When included as a cathode active material, this additional lithium content also controls the capacity of the powder. It should be understood that sufficient lithium should be present to react with and sinter the precursor particles, but without the risk of over-sintering. Over-sintering can produce solid clumps. Even if solid clumps can be avoided, excess lithium can reduce the capacity and efficiency of the cathode active material.
[0233] Particle density and strength increase with increasing molar ratio (i.e., α). Figure 17 A set of scanning electron micrographs according to an exemplary embodiment are presented, showing the effect of temperature and molar ratio (α) on particle morphology. The powder composition (i.e., the particles therein) corresponds to x = 0.04, and α gradually increases from 1.00 to 1.04, to 1.06, to 1.08, and to 1.10 (i.e., Figure 17 (From left to right in the middle). Two temperatures are shown, namely 1050℃ and 1100℃. Oxygen in the composition can correspond to δ=2, but variations from this stoichiometry are also possible (i.e., within 1.90≤δ≤2.20).
[0234] Heating temperature can affect the surface morphology of powders and increase tap density. Figure 17 In the illustrated embodiment, at 1050°C and an α value less than 1.02, the secondary particles flow freely after calcination. However, the primary grains do not exhibit good bonding strength. At larger molar ratios, however, individual grains fuse together better. At 1100°C, the secondary particles have smooth surfaces and well-bonded grains. As the molar ratio increases (i.e., at 1100°C), the secondary particles begin to agglomerate, forming a rigid sintered agglomerate of particles. This rigid sintered agglomerate can be broken up by grinding.
[0235] In some embodiments, 1.00 ≤ α ≤ 1.05. In other embodiments of the method, 1.00 < α ≤ 1.10. In still other embodiments, 1.00 < α ≤ 1.05.
[0236] In some implementations, 1.01 ≤ α ≤ 1.05 and 0.02 ≤ x ≤ 0.05. In other implementations, 1.01 ≤ α ≤ 1.05 and x = 0.04.
[0237] Figure 18 Presented a representation of the mixing comparison according to the exemplary implementation, including Li α Co 0.96 Mn0.04 O δ is a graph of data on the influence of the capacity and efficiency of the cathode active material. The mixing ratio corresponds to the ratio at which the lithium source is mixed with the precursor particles. The cathode active material comprises Figure 17 the powder shown and calcined at 1050°C. The oxygen in the composition may correspond to δ=2, but variations from this stoichiometry are also possible (i.e., within 1.90≤δ≤2.20).
[0238] In Figure 18 , the abscissa shows that the mixing ratio increases from 1.00 to 1.10. At a mixing ratio of 1.04 (corresponding to α=1.01 as measured by ICP-OES), the cathode active material has a maximum discharge capacity of 192 mAh / g (i.e., during discharge from 4.5V to 2.75V). For mixing ratios of 1.06, 1.08 and 1.10 (i.e., α=1.02, 1.03 and 1.04 as measured by ICP-OES, respectively), high discharge values of about 190 mAh / g can also be obtained.
[0239] In some variations, the present disclosure relates to a compound represented by formula (VII):
[0240] Li α Co 1-x-y M y Mn x O δ (VII)
[0241] wherein 0.95≤α≤1.30, 0<x≤0.30, 0≤y≤0.10, and 1.98≤δ≤2.04, and M is at least one element selected from the group consisting of B, Na, Mg, Ti, Ca, V, Cr, Fe, Co, Ni, Cu, Zn, Al, Sc, Y, Ga, Zr, Ru and Mo. The compound of formula (VII) is single-phase. The compound may have a trigonal crystal structure. In other variations, 0.98≤α≤1.16 and 0<x≤0.16. In some variations, 0.98≤α≤1.16, 0<x≤0.16, 0<y≤0.05, 1.98≤δ≤2.04
[0242] In some variations, the present disclosure relates to a compound represented by formula (VIII):
[0243] Li α Co 1-x-y Al y Mn x O δ (VIII)
[0244] where 0.95≤α≤1.30, 0<x≤0.30, 0≤y≤0.10, and 1.98≤δ≤2.04. In some variations, 0.96≤α≤1.04, 0<x≤0.10, 0≤y≤0.10, and 1.98≤δ≤2.04. In some variations, for the compound represented by formula (VIII), 0.98≤α≤1.01, 0.02≤x≤0.04, 0≤y≤0.03, and 1.98≤δ≤2.04. The compound of formula (VIII) is single-phase. The compound may have a trigonal crystal structure.
[0245] In some cases, for the compounds represented by formulae (VII) and (VIII), α>1+x. In other cases, α<1+x. Thus, α in formulae (VII) and (VIII) can deviate from α=1+x, which may be associated with a solid solution of Li₂MnO₃ and (1-x)LiCo 1-y M y O₂. The solid solution can be represented by xLi₂MnO₃·(1-x)LiCo 1-y M y O₂ and xLi₂MnO₃·(1-x)Li 1-y Co 1- y M y O₂, or in compact notation by Li 1+x Co 1-x-y+xy M (1-x) * y Mn x O 2+x or Li 1+x-y+xy Co 1-x-y+xy M (1-x)*y Mn x O 2+x .
[0246] As noted above, the various compounds do not include a second phase, such as a second phase with a different crystal structure. It should be understood that Li₂MnO₃ is a "rock salt" phase with a monoclinic C2 / m crystal structure. Thus, the cathode active material based on the solid solution between Li₂MnO₃ and LiCo 1-y M y O₂ has portions that exhibit the "rock salt" phase of the monoclinic C2 / m crystal structure. This "rock salt" phase appears in addition to any phase associated with LiCo 1-y M y O₂, making the solid solution biphasic (or multiphase). In contrast, the cathode active materials represented by formulae (VII) and (VIII) and variations thereof are single-phase and only have a trigonal crystal structure.
[0247] To stabilize compounds of formulas (VII) and (VIII), it is not desirable to be limited to any particular mechanism or mode of action. The compound has a crystalline structure, but other components of M may also contribute to its stability. Manganese is uniformly distributed within the compound. The crystal structure includes a cobalt sublattice. Alternatively, in some variations, aggregates of manganese (e.g., pair, triplet, etc.) appear in the Co sublattice and are uniformly distributed therein. These aggregates can be detected, for example, by nuclear magnetic resonance (NMR), as described herein. The presence of manganese in the compound can limit emissions during battery operation (e.g., charging, discharging, etc.). A phase transition occurs in the crystal structure. The presence of Mn can also improve the oxidative stability of the compound at higher voltages (e.g., equal to or greater than 4.0 volts).
[0248] In some variations, x corresponds to the degree of Mn substitution for Co. The degree of Mn substitution can be related to the stability of the compound when used in cathode active materials. In various respects, Mn substitution for Co can be greater than or equal to the lower substitution limit. Alternatively, Mn substitution for Co can be equal to or less than the substitution limit.
[0249] In some variations, x is at least 0.001. In some variations, x is at least 0.01. In some variations, x is at least 0.02. In some variations, x is at least 0.03. In some variations, x is at least 0.04. In some variations, x is at least 0.05. In some variations, x is at least 0.06. In some variations, x is at least 0.07. In some variations, x is at least 0.08. In some variations, x is at least 0.09. In some variations, x is at least 0.10. In some variations, x is at least 0.12. In some variations, x is at least 0.14. In some variations, x is at least 0.16. In some variations, x is at least 0.18. In some variations, x is at least 0.20. In some variations, x is at least 0.22. In some variations, x is at least 0.24. In some variations, x is at least 0.26. In some variations, x is at least 0.28.
[0250] In some variations, x is less than or equal to the upper limit of substitution. In some variations, x is less than or equal to 0.30. In some variations, x is less than or equal to 0.28. In some variations, x is less than or equal to 0.26. In some variations, x is less than or equal to 0.24. In some variations, x is less than or equal to 0.22. In some variations, x is less than or equal to 0.20. In some variations, x is less than or equal to 0.18. In some variations, x is less than or equal to 0.16. In some variations, x is less than or equal to 0.14. In some variations, x is less than or equal to 0.12. In some variations, x is less than or equal to 0.10. In some variations, x is less than or equal to 0.09. In some variations, x is less than or equal to 0.08. In some variations, x is less than or equal to 0.07. In some variations, x is less than or equal to 0.06. In some variations, x is less than or equal to 0.05. In some variations, x is less than or equal to 0.04. In some variations, x is less than or equal to 0.03.
[0251] It should be understood that in any combination, the lower and upper limits can be replaced by any of the above variations to define the range of x. For example, but not limited to, x can be in the range of 0.001 to 0.01. x can be in the range of 0.02 to 0.05 (i.e., 0.02 ≤ x ≤ 0.07). In another non-limiting example, x can be in the range of 0.24 to 0.28 (i.e., 0.06 ≤ x ≤ 0.10). In another non-limiting example, x can be in the range of 0.24 to 0.28 (i.e., 0.22 ≤ x ≤ 0.28). Other combinations of upper and lower limits are also possible.
[0252] Furthermore, to avoid being limited to any particular mechanism or mode of action, a certain amount of lithium can be selected in the compounds of formulas (VII) and (VIII) to stabilize them. The crystal structure is improved, and battery performance is enhanced. The lithium content can be selectively adjusted to compensate for the degree of substitution of Co (i.e., via substitution with Mn, M, or Al). For example, but not limited to, α can be selected to be approximately 1+x. This selection, relative to α=1, can improve... The stability of the crystal structure during lithiation and delithiation (see...) Figure 29 In another non-limiting example, αδ can be chosen to be greater than 1+x to accommodate substitutions other than Mn (i.e., M and y). These substitutions can result in compounds with improved discharge energies (see [link to relevant documentation]). Figure 33 In yet another example, the lithium content can be selected based on α < 1 + x to enhance battery performance. For example... Figure 30 As shown, Li 1.003 Co 0.97 Mn 0.03 O2 compared to Li 1.014 Co 0.97 Mn 0.03O2 maintains a higher discharge energy after repeated cycles, but the latter has a higher α value. In some variants, 0.98 ≤ Li / Me ≤ 1.01.
[0253] It should be understood that α corresponds to the ratio of lithium to Co and its substitutes (i.e., M and Mn for formula (VII), and M, Mn, and Al for formula (VIII). For formula (VII), this ratio can be described as [Li] / [Co]. 1-x-y M y Mn x For equation (VII), this ratio can be described as [Li] / [Co]. 1-x-y Al y Mn x For compounds with y = 0, α corresponds to the ratio of lithium to Co and Mn, i.e., [Li] / [Co]. 1-x Mn x This latter ratio can be referred to as the lithium to transition metal ratio (i.e., Li / TM).
[0254] In some variants, the compound remains a single phase and has a triangular shape. Crystal structure. In some variations, α may be equal to or greater than the lower limit. In some variations, α is at least 0.95. In some variations, α is at least 0.98. In some variations, α is at least 1.00. In some variations, α is greater than 1.00. In some variations, α is at least 1.02. In some variations, α is at least 1.04. In some variations, α is at least 1.06. In some variations, α is at least 1.08. In some variations, α is at least 1.10. In some variations, α is at least 1.12. In some variations, α is at least 1.14. In some variations, α is at least 1.16. In some variations, α is at least 1.20. In some variations, α is at least 1.22. In some variations, α is at least 1.24. In some variations, α is at least 1.26. In some variations, α is at least 1.28.
[0255] Similarly, α can be less than or equal to the lower limit. In some variations, α is less than or equal to 1.30. In some variations, α is less than or equal to 1.28. In some variations, α is less than or equal to 1.26. In some variations, α is less than or equal to 1.24. In some variations, α is less than or equal to 1.22. In some variations, α is less than or equal to 1.20. In some variations, α is less than or equal to 1.16. In some variations, α is less than or equal to 1.14. In some variations, α is less than or equal to 1.12. In some variations, α is less than or equal to 1.10. In some variations, α is less than or equal to 1.08. In some variations, α is less than or equal to 1.06. In some variations, α is less than or equal to 1.04. In some variations, α is less than or equal to 1.02. In some variations, α is less than or equal to 1.00. In some variants, α is less than 1.00. In some variants, α is less than or equal to 0.98. In these variants, the compound also remains a single phase and has a triangular shape. Crystal structure.
[0256] It should be understood that α can replace the lower and upper limits in any of the above variations to define the range. For example, but not limited to, α can be in the range of 0.95 to 1.00 (i.e., 0.95 ≤ α ≤ 1.00). In another non-limiting example, α can be in the range of 1.00 to 1.06 (i.e., 1.00 ≤ α ≤ 1.08). In another non-limiting example, α can be in the range of 1.22 to 1.28 (i.e., 1.22 ≤ α ≤ 1.28). Other combinations of the upper and lower limits are also possible.
[0257] It should also be understood that the specific upper and lower limits of x and α can be combined in any of the above variations to define the ranges of x and α. For example, but not limited to, x ≥ 0.03 and 0.98 ≤ α ≤ 1.10. In another non-restrictive example, 0.02 ≤ x ≤ 0.10 and 0.95 ≤ α ≤ 1.12. In another non-restrictive example, 0.04 ≤ x ≤ 0.12 and 0.95 ≤ α ≤ 1.16. Other range combinations are also possible.
[0258] In some variations, α is close to 1+x. In these variations, α may be close to 1+x and the tolerance is no greater than 5%. The tolerance may correspond to (1–t)*(1+x)≤α≤(1+x)*(1+t), where t≤0.05. In some variations, the tolerance is less than or equal to ±5.0%. In some cases, the tolerance is less than or equal to ±4.5%. In some cases, the tolerance is less than or equal to ±4.0%. In some cases, the tolerance is less than or equal to ±3.5%. In some cases, the tolerance is less than or equal to ±3.0%. In some cases, the tolerance is less than or equal to ±2.5%. In some cases, the tolerance is less than or equal to ±2.0%. In some cases, the tolerance is less than or equal to ±1.5%. In some cases, the tolerance is less than or equal to ±1.0%.
[0259] In some cases, the tolerance is at least ±1.0%. In some cases, the tolerance is at least ±0.5%. In some cases, the tolerance is at least ±1.0%. In some cases, the tolerance is at least ±1.5%. In some cases, the tolerance is at least ±2.0%. In some cases, the tolerance is at least ±2.5%. In some variations, the tolerance is at least ±3.0%. In some cases, the tolerance is at least ±3.5%. In some cases, the tolerance is at least ±4.0%. In some cases, the tolerance is at least ±4.5%.
[0260] It should be understood that when α approaches 1+x, the corresponding compound retains its single-phase characteristics and does not contain Li₂MnO₃. Furthermore, the compound exhibits improved phase transition resistance and improved discharge energy during charging and discharging. Non-limiting examples of such compounds include Li 1.050 Co 0.96 Mn 0.04 O2, Li 1.074 Co 0.96 Mn 0.04 O2, Li 1.197 Co 0.78 Mn 0.22 O2 and Li 1.247 Co 0.72 Mn 0.28 O2.
[0261] In some variants, the compound is selected from Li 1.050 Co 0.96 Mn 0.04 O2, Li 1.074 Co 0.96 Mn 0.04 O2, Li 1.081 Co 0.96 Mn 0.04 O2, Li 1.089 Co 0.96 Mn 0.04O2, Li 1.050 Co 0.93 Mn 0.07 O2, Li 1.065 Co 0.90 Mn 0.10 O2, Li 1.100 Co 0.90 Mn 0.10 O2, Li 1.110 Co 0.90 Mn 0.10 O2, Li 1.158 Co 0.90 Mn 0.10 O2, Li 0.975 Co 0.84 Mn 0.16 O2, Li 1.050 Co 0.84 Mn 0.16 O2, Li 1.114 Co 0.84 Mn 0.16 O2, Li 1.197 Co 0.78 Mn 0.22 O2, Li 1.190 Co 0.72 Mn 0.28 O2 and Li 1.247 Co 0.72 Mn 0.28 O2. In these compounds, manganese substitutes for cobalt and does not induce the formation of Li2MnO3; that is, the compounds are single-phase and have a triangular shape. Crystal structure.
[0262] In some variants, the compound is Li 0.991 Mn 0.03 Co 0.97 O2. In some variants, the compound is Li. 0.985 Mn 0.03 Co 0.97 O2.
[0263] This disclosure also relates to powders comprising the compounds described herein. In various aspects, this disclosure relates to powders comprising particles containing any of the compounds described above. The powder may be used as part or all of a cathode active material (i.e., a cathode active material comprising a powder).
[0264] Compounds and powders can be used as cathode active materials for lithium-ion batteries, as described herein. These cathode active materials contribute to energy storage by releasing and storing lithium ions during the charging and discharging of lithium-ion batteries, respectively.
[0265] Without being limited to a specific mechanism or mode of action, the compounds can improve the volumetric energy density, energy retention, and / or cycle performance of cathode active materials during the charging and discharging of battery cells. The compounds can also improve the thermal stability of cathode active materials.
[0266] In some variations, the particles have an average particle size greater than or equal to the first lower limit. In some variations, the particles have an average diameter of at least 5 μm. In some variations, the particles have an average diameter of at least 10 μm. In some variations, the particles have an average diameter of at least 15 μm. In some variations, the particles have an average diameter of at least 20 μm. In some variations, the particles have an average diameter of at least 25 μm.
[0267] In some variations, the particles have an average particle size less than or equal to the first upper limit. In some variations, the particles have an average diameter less than or equal to 30 μm. In some variations, the particles have an average diameter less than or equal to 25 μm. In some variations, the particles have an average diameter less than or equal to 20 μm. In some variations, the particles have an average diameter less than or equal to 15 μm. In some variations, the particles have an average diameter less than or equal to 10 μm. In some variations, the particles have an average diameter less than or equal to 5 μm.
[0268] It should be understood that the first lower limit and the first upper limit can be combined in any of the above variations to define a first range of average particle size. For example, but not limited to, the average particle size can be in the range of 10 μm to 20 μm. In another non-limiting example, the average particle size can be in the range of 20 μm to 25 μm. Other ranges are also possible. Particles having the aforementioned average particle size, whether characterized by the first lower limit, the first upper limit, or both (i.e., the first range), can be treated according to the coprecipitation method.
[0269] In some variations, the particles have an average particle size greater than or equal to the second lower limit. In some variations, the particles have an average diameter of at least 200 nm. In some variations, the particles have an average diameter of at least 300 nm. In some variations, the particles have an average diameter of at least 400 nm. In some variations, the particles have an average diameter of at least 500 nm. In some variations, the particles have an average diameter of at least 600 nm. In some variations, the particles have an average diameter of at least 700 nm.
[0270] In some variations, the particles have an average particle size less than or equal to the second upper limit. In some variations, the particles have an average diameter less than or equal to 800 nm. In some variations, the particles have an average diameter less than or equal to 700 nm. In some variations, the particles have an average diameter less than or equal to 600 nm. In some variations, the particles have an average diameter less than or equal to 500 nm. In some variations, the particles have an average diameter less than or equal to 400 nm. In some variations, the particles have an average diameter less than or equal to 300 nm.
[0271] It should be understood that the second lower limit and the second upper limit can be combined in any of the above variations to define a second range of average particle size. For example, but not limited to, the average particle size can be in the range of 300 nm to 500 nm. In another non-limiting example, the average particle size can be in the range of 400 nm to 800 nm. Other ranges are also possible. Particles having the aforementioned average particle size, whether characterized by the second lower limit, the second upper limit, or both (i.e., the second range), can be processed according to the sol-gel method.
[0272] In some variations, the particles are secondary particles formed from agglomerated primary particles. The agglomerated primary particles can be sintered together. In some cases, the secondary particles have an average particle size greater than or equal to a lower limit. Non-limiting examples of the lower limit include 15 μm, 20 μm, and 25 μm. In some cases, the secondary particles have an average particle size less than or equal to an upper limit. Non-limiting examples of the upper limit include 30 μm, 25 μm, and 20 μm. It should be understood that the lower and upper limits can be combined in any of the above variations to define a range of average particle size. For example, but not limited to, the average particle size can be in the range of 15 μm to 20 μm. In another non-limiting example, the average particle size can be in the range of 20 μm to 25 μm. Other ranges are also possible.
[0273] In some variations, a single primary particle occupies a certain percentage of the volume occupied by the corresponding secondary particle. In some cases, this percentage is greater than or equal to a lower limit. In some variations, a single primary particle occupies at least 30% of the volume occupied by the corresponding secondary particle. In some variations, a single primary particle occupies at least 35% of the volume occupied by the corresponding secondary particle. In some variations, a single primary particle occupies at least 40% of the volume occupied by the corresponding secondary particle. In some variations, a single primary particle occupies at least 45% of the volume occupied by the corresponding secondary particle. In some variations, a single primary particle occupies at least 50% of the volume occupied by the corresponding secondary particle. In some variations, a single primary particle occupies at least 55% of the volume occupied by the corresponding secondary particle. In some variations, a single primary particle occupies at least 60% of the volume occupied by the corresponding secondary particle. In some variations, a single primary particle occupies at least 65% of the volume occupied by the corresponding secondary particle.
[0274] In some variations, a single primary particle occupies less than or equal to 70% of the volume occupied by the corresponding secondary particle. In some variations, a single primary particle occupies less than or equal to 65% of the volume occupied by the corresponding secondary particle. In some variations, a single primary particle occupies less than or equal to 60% of the volume occupied by the corresponding secondary particle. In some variations, a single primary particle occupies less than or equal to 55% of the volume occupied by the corresponding secondary particle. In some variations, a single primary particle occupies less than or equal to 50% of the volume occupied by the corresponding secondary particle. In some variations, a single primary particle occupies less than or equal to 45% of the volume occupied by the corresponding secondary particle. In some variations, a single primary particle occupies less than or equal to 40% of the volume occupied by the corresponding secondary particle. In some variations, a single primary particle occupies less than or equal to 35% of the volume occupied by the corresponding secondary particle.
[0275] It should be understood that the lower and upper limits can be combined in any of the above variations to define the range of percentages. For example, but not limited to, the percentage can be in the range of 30% to 50%. However, other ranges are also possible.
[0276] As described in this article, larger particle sizes and a higher percentage of secondary particles consisting of a single primary particle can be achieved by using higher sintering temperatures. It is undesirable to be limited by a specific mechanism or mode of action, where particles are less prone to fracture in some cases, thus providing enhanced stability compared to conventional particles.
[0277] Including Mn and / or aluminum to replace Co, altering the amount of lithium, and / or including an Al2O3 coating in the compound can reduce or potentially reduce unstable phase transitions. If it is not desirable to be limited to a specific mechanism or mode of action, additional elements can also provide greater oxidation stability to the compound at higher battery cutoff voltages. In some variants, for at least 4.4V and Li 0 / Li + In such cases, compounds, particles, and / or cathode active materials may exhibit increased stability.
[0278] In some variations, the particles exhibit increased particle strength. When used in cathode active materials, this increased particle strength leads to a higher energy retention rate.
[0279] In some variations, the increased amount of Mn in the cathode active material provides improved battery stability. In some variations, the increased Mn content raises the decomposition onset temperature. In some variations, the increased Mn content can lead to a reduction in heat release from the compound at the decomposition temperature.
[0280] In some variations, the cathode active material has a first-cycle discharge energy of at least 700 Wh / kg. In some variations, the cathode active material has a first-cycle discharge energy of at least 725 Wh / kg. In some variations, the cathode active material has a first-cycle discharge energy of at least 750 Wh / kg. In some variations, the cathode active material has a first-cycle discharge energy of at least 775 Wh / kg. In some variations, the cathode active material has a first-cycle discharge energy of at least 800 Wh / kg. In some variations, the cathode active material has a first-cycle discharge energy of at least 825 Wh / kg. In some variations, the cathode active material has a first-cycle discharge energy of at least 850 Wh / kg. In some variations, the cathode active material has a first-cycle discharge energy of at least 875 Wh / kg.
[0281] In some variations, the cathode active material has a first cycle discharge capacity of at least 180 mAh / g. In some variations, the cathode active material has a first cycle discharge capacity of at least 185 mAh / g. In some variations, the cathode active material has a first cycle discharge capacity of at least 190 mAh / g. In some variations, the cathode active material has a first cycle discharge capacity of at least 195 mAh / g. In some variations, the cathode active material has a first cycle discharge capacity of at least 200 mAh / g. In some variations, the cathode active material has a first cycle discharge capacity of at least 205 mAh / g. In some variations, the cathode active material has a first cycle discharge capacity of at least 210 mAh / g. In some variations, the cathode active material has a first cycle discharge capacity of at least 215 mAh / g.
[0282] In some variations, the cathode active material retains at least 65% of its energy capacity after 52 charge-discharge cycles. In some variations, the cathode active material retains at least 67% of its energy capacity after 52 charge-discharge cycles. In some variations, the cathode active material retains at least 69% of its energy capacity after 52 charge-discharge cycles. In some variations, the cathode active material retains at least 71% of its energy capacity after 52 charge-discharge cycles. In some variations, the cathode active material retains at least 73% of its energy capacity after 52 charge-discharge cycles. In some variations, the cathode active material retains at least 75% of its energy capacity after 52 charge-discharge cycles. In some variations, the cathode active material retains at least 77% of its energy capacity after 52 charge-discharge cycles. In some variations, the cathode active material retains at least 79% of its energy capacity after 52 charge-discharge cycles. In some variations, the cathode active material retains at least 81% of its energy capacity after 52 charge-discharge cycles. In some variations, the cathode active material retains at least 83% of its energy capacity after 52 charge-discharge cycles.
[0283] Compounds, powders, and cathode active materials can be used in batteries as described herein. The materials can be used in electronic devices. Electronic devices as used herein can refer to any electronic device known in the art, including portable electronic devices. For example, an electronic device can be a telephone such as a mobile phone and a landline phone, or any communication device such as a smartphone (including, for example, an iPhone). TM Electronic devices can also be entertainment devices, including portable DVD players, conventional DVD players, Blu-ray players, video game controllers, and music players such as portable music players (e.g., Electronic devices may be part of a display, such as a digital display, television monitor, e-book reader, or portable web browser (e.g., Electronic devices can also be part of a control system, such as a watch (e.g., Apple Watch) or a computer monitor. They can also be part of a device that provides control, such as controlling the streaming of images, video, or sound (e.g., Apple Watch). This can be for remote control of electronic devices. Furthermore, electronic devices can be part of a computer or its accessories, such as hard drive tower enclosures or protective cases, laptop computer cases, laptop computer keyboards, laptop computer touchpads, desktop computer keyboards, mice, and speakers. Batteries and battery packs can also be used in devices such as watches or clocks. Components powered by batteries or battery packs can include, but are not limited to, microprocessors, computer-readable storage media, input and / or output devices such as keyboards, touchpads, touchscreens, mice, speakers, etc.
[0284] Example
[0285] The following examples are for illustrative purposes only. It will be apparent to those skilled in the art that various modifications can be made to both the materials and methods without departing from the scope of this disclosure.
[0286] Example 1—Wet impregnation to form an Al2O3 coating
[0287] While stirring, add deionized water (Millipore ultrapure water, 18 MΩ·cm) dropwise to 10g of base powder (i.e., 10g Li). 1.04 Co 0.96 Mn 0.04 O 2.04 Add the base powder. Stop stirring when the powder is wetted but still loose. (Stop adding deionized water before the powder forms soft, sticky lumps.) Then calculate the ratio R, which is equal to the amount of water added (by weight or volume) divided by the amount of base powder. The amount of water required to wet the powder to the appropriate moisture level depends on the surface area of the base powder used. Generally, a larger surface area requires more water.
[0288] Next, a certain amount (e.g., by weight) of base powder is selected. The amount of aluminum salt precursor (e.g., aluminum nitrate nonahydrate) is determined to correspond to the desired level of Al2O3 coating on the desired amount of base powder (e.g., 0.1% by weight). The amount of deionized water is then calculated using a ratio (i.e., R multiplied by the weight of the base powder). Table 1 shows the type and amount of base powder, solvent (i.e., deionized water), and aluminum salt precursor.
[0289] Then measure the quantities given in Table 1, including the predetermined amount of deionized water. Dissolve aluminum nitrate nonahydrate in deionized water to form a clear solution. While stirring, add the clear solution dropwise to the base powder in the glass container. After the clear solution has been added, continue stirring the base powder for a few minutes to ensure thorough mixing. A moistened, loose powder is formed.
[0290] The moistened, loose powder was dried overnight in an oven at 80°C. The dried powder was then transferred to an Al₂O₃ crucible and heat-treated at 120°C for 2 hours. Following this heat treatment, a subsequent heat treatment was performed at 500°C for 4 hours in stagnant air. The heat-treated powder was then passed through a 325-mesh sieve. Occasionally, light grinding with a mortar and pestle was necessary to break up any agglomerated portions of the heat-treated powder.
[0291] Table 1. For use in 10g Li 1.04 Co 0.96 Mn 0.04 Material with 0.1 wt% Al2O3 coating on O2
[0292] Base powder <![CDATA[Li 1.04 What 0.96 Mn 0.04 O2]]> 10g Solvent (used to dissolve coating precursors) Deionized water ~0.9–1 mL or g Coating precursor <![CDATA[Al(NO3)3·9H2O]]> 0.075g
[0293] Example 2—Wet impregnation to form an AlF3 coating
[0294] The ratio R is determined according to the procedure described in Example 1.
[0295] Next, a certain amount (e.g., by weight) of base powder is selected. The amounts of aluminum salt precursor (e.g., aluminum nitrate nonahydrate) and fluoride salt precursor (e.g., aluminum fluoride) are determined to correspond to the desired level of AlF3 coating on the base powder (e.g., 0.1% by weight). To ensure complete reaction, the amount of fluoride salt precursor in AlF3 is twice the stoichiometric amount of fluoride (i.e., the molar ratio of Al to F is chosen to be 1:6). The required amount of deionized water is then calculated using a ratio (i.e., R multiplied by the weight of the base powder).
[0296] Aluminum nitrate nonahydrate was dissolved in a first portion of deionized water to form a first clear solution. Ammonium fluoride was dissolved in a second portion of deionized water to form a second clear solution. The base powder was transferred to a glass container, and the first clear solution was rapidly added to it in droplet form (i.e., to "submerge" the base powder). The base powder was stirred for 2 minutes and dried at 105°C to obtain a cake.
[0297] The powder cake is broken into loose powder (e.g., using a mortar and pestle) and then transferred to a fresh glass container. The fresh glass container is gently tapped to hold the loose powder. While stirring, a second clear solution is rapidly added to the powder in the glass container (i.e., similar to the first clear solution). The mixture is stirred for 2 minutes and then dried at 105°C. The dried powder is transferred to an aluminum crucible and heat-treated at 120°C for 2 hours under flowing nitrogen. The heat-treated powder is then heated at 400°C for 5 hours to obtain a heat-treated powder cake. The heat-treated powder cake is easily broken down, lightly ground, and sieved through a 325-mesh sieve.
[0298] Example 3—Wet impregnation to form an AlPO4 coating
[0299] A predetermined amount of base material powder (i.e., Li) is applied. 1.04 Co 0.96 Mn 0.04O2) is weighed into a glass container. Based on the weighed amount of base powder, the amounts of aluminum precursor and phosphate precursor required to achieve the desired AlPO4 coating amount (e.g., 5% by weight) are calculated. The aluminum precursors used include various aluminum salts, such as aluminum nitrate, aluminum acetate, or other aluminum salts soluble in water or alcohol. The phosphate precursors used are ammonium dihydrogen phosphate (NH4H2PO4), diammonium hydrogen phosphate [(NH4)2HPO4], or a combination of both. The molar ratio of Al to P is maintained between 0.9 and 1.1. The aluminum precursor and phosphate precursor are separately dissolved in a small amount of water or alcohol to form solutions. The two solutions are then mixed together. The pH of the mixed solution is adjusted by varying the ratio of the ammonium phosphate salt to prevent precipitation. The base powder is stirred with a glass rod or spatula while the mixed solution is added dropwise to the base powder. The volume of the solution is such that the base powder is initially wetted and thoroughly mixed (i.e., exhibiting a wet consistency). After drying at 50-80℃, the dried base powder is heat-treated at 700℃ for 5 hours in stagnant air.
[0300] Example 4—Wet impregnation to form a Co3(PO4)2 coating
[0301] A predetermined amount of base material powder (i.e., Li) is applied. 1.04 Co 0.96 Mn 0.04 O2) is weighed into a glass container. Based on the weighed amount of base powder, the amounts of cobalt precursor and phosphate precursor required for the desired Co3(PO4)2 coating amount (e.g., 5% by weight) are calculated. The cobalt precursors used include various cobalt salts, such as cobalt nitrate, cobalt acetate, or other cobalt salts soluble in water or alcohol. The phosphate precursors used are ammonium dihydrogen phosphate (NH4H2PO4), diammonium hydrogen phosphate [(NH4)2HPO4], or a combination of both. The molar ratio of Co to P is maintained between 1.4 and 1.6. The cobalt precursor and phosphate precursor are separately dissolved in a small amount of water or alcohol to form solutions. The two solutions are then mixed together. The pH of the mixed solution is adjusted by varying the ratio of the ammonium phosphate salt to prevent precipitation. The base powder is stirred with a glass rod or spatula while the mixed solution is added dropwise to the base powder. The volume of solution added is sufficient to initially wet and thoroughly mix the base powder (i.e., exhibit a wet consistency). After drying at 50-80℃, the dried base powder is then heat-treated in stagnant air at 700℃ for 5 hours.
[0302] Example 5—Wet impregnation to form a Li-Al2O3 coating
[0303] A predetermined amount of base material powder (i.e., Li) is applied. 1.04 Co 0.96 Mn 0.04O2) is weighed into a glass beaker. The amount of aluminum precursor required for the desired coating amount (e.g., 0.5 wt%) is calculated based on the amount of base powder weighed. Aluminum precursors include various aluminum salts, such as aluminum nitrate, aluminum acetate, or other aluminum salts soluble in water or alcohol. The aluminum precursor is dissolved in a small amount of water or alcohol to form a first clear solution. The desired amount of lithium precursor is calculated using a Li to Al molar ratio between 0.25 and 1.05. The lithium precursor used is lithium hydroxide, lithium nitrate, lithium acetate, or other lithium salts soluble in water or alcohol. The required amount of lithium precursor is dissolved in a small amount of water or alcohol to form a second clear solution. The first and second clear solutions are mixed together. The mixture is then added dropwise to the base powder while stirring. The volume of solution added is such that the base powder is initially wetted but not softened (i.e., exhibits a wet consistency). After drying at 50–80°C, the dried base powder is then heat-treated in stagnant air to 500°C for 4 hours. The pH of the first clarified solution (i.e., the aluminum solution) can also be changed to improve coating properties such as coating density and uniformity.
[0304] Example 6—Wet impregnation to form a Li-Co3(PO4)2 coating
[0305] A predetermined amount of base material powder (i.e., Li) is applied. 1.04 Co 0.96 Mn 0.04 O2) is weighed into a glass beaker. Based on the weighed amount of base powder, the amounts of cobalt precursor, phosphate precursor, and lithium precursor required for the desired coating amount (e.g., 0.5 wt%) are calculated. Cobalt precursors include various cobalt salts, such as cobalt nitrate, cobalt acetate, or other cobalt salts soluble in water or alcohol. The phosphate precursors used are ammonium dihydrogen phosphate (NH4H2PO4), diammonium hydrogen phosphate [(NH4)2HPO4], lithium phosphate, or combinations thereof. The molar ratio of Co to P is maintained between 1.4 and 1.6. The desired amount of lithium precursor is calculated using a Li to Co molar ratio between 0.3 and 1.05. The lithium precursors used are lithium hydroxide, lithium nitrate, lithium acetate, or other lithium salts soluble in water or alcohol. The cobalt precursor, phosphate precursor, and lithium precursor are each dissolved separately in a small amount of water or alcohol to form the corresponding clear solutions. The three solutions are then mixed together. The mixture is then added dropwise to the base powder while stirring. The volume of the added solution is sufficient to initially wet the base powder, but not to make it soft (i.e., exhibiting a wet consistency). After drying at 50-80°C, the dried base powder is heat-treated in stagnant air at 700°C for 5 hours.
[0306] Example 7—Suspension treatment to form an Al2O3 coating
[0307] Aqueous Al(NO3)3 solution and base powder (Li 1.02 Co 0.96 Mn 0.04The O2 suspension was mixed and then pumped into a stirred tank reactor. While stirring, an ammonia solution was used via a feedback pump to maintain the reaction pH at 9.3. The suspension was stirred for 2 hours, filtered, dried, and calcined in air at 400°C for 5 hours.
[0308] Example 8—Suspension treatment to form a Co3(PO4)2 coating
[0309] The first Co(NO3)3 aqueous solution and the second ammonium dihydrogen phosphate aqueous solution were pumped into the base powder (Li) in the stirred tank reactor. 1.02 Co 0.96 Mn 0.04 The mixture was placed in an O2 suspension. The combined volumes were stirred for 2 hours, filtered, and dried. The dried powder was then calcined in air at 700°C for 5 hours.
[0310] Example 9—Suspension treatment to form an AlPO4 coating
[0311] The first Al(NO3)3 aqueous solution and the second ammonium dihydrogen phosphate solution were pumped into the stirred tank reactor to add the base powder (Li). 1.02 Co 0.96 Mn 0.04 The mixture was placed in an O2 suspension. The combined volumes were stirred for 2 hours, filtered, and dried. The dried powder was then calcined in air at 700°C for 5 hours.
[0312] Example 10—Dry processing to form an Al2O3 coating
[0313] A predetermined amount of base powder (Li) 1.02 Co 0.96 Mn 0.04 Al₂O₃ nanocrystal powder was weighed and poured into a dry coating machine (Nobilta, NOB-130, Hosokawa Micron Ltd). Next, Al₂O₃ nanocrystal powder was weighed according to the desired coating amount on the predetermined base powder (e.g., 0.5 wt%). The weighed Al₂O₃ nanocrystal powder was poured into the dry coating machine. The dry coating machine includes a high-speed rotary mixer that mechanically binds the Al₂O₃ nanocrystal powder particles to the particles in the base powder (i.e., along its surface). For a 0.5 wt% coating, 2.5 g of Al₂O₃ nanocrystal powder was thoroughly mixed with 500 g of base powder. The speed was controlled at 4000 rpm. After 5 minutes, a base powder coated with Al₂O₃ was formed.
[0314] Example 11—Dry processing to form an AlF3 coating
[0315] A predetermined amount of base powder (Li) 1.02 Co 0.96 Mn 0.04O2) was weighed and poured into a dry coating machine (Nobilta, NOB-130, Hosokawa Micron Ltd). Next, AlF3 nanocrystal powder was weighed according to the desired coating amount on the predetermined base powder (e.g., 0.1 wt%). The weighed AlF3 nanocrystal powder was poured into the dry coating machine. For a 0.1 wt% coating, 0.5 g of AlF3 was thoroughly mixed with 500 g of base powder. The speed was controlled at 4000 rpm. After 5 minutes, a base powder coated with AlF3 was formed.
[0316] Example 12—Dry processing to form coatings of Al2O3 and AlF3
[0317] A predetermined amount of base powder (Li) 1.02 Co 0.96 Mn 0.04 Al₂O₃ and AlF₃ nanocrystalline powders were weighed and poured into a dry coating machine (Nobilta, NOB-130, Hosokawa Micron Ltd). Next, Al₂O₃ and AlF₃ nanocrystalline powders were weighed according to the desired coating amount on the base powder (e.g., 0.1 wt%). The weighed nanocrystalline powders were poured into the dry coating machine. For a 0.1 wt% coating, 0.25 g of Al₂O₃ and 0.05 g of AlF₃ were thoroughly mixed with 500 g of base powder. The speed was controlled at 4000 rpm. After 5 minutes, a base powder coated with Al₂O₃ and AlF₃ was formed.
[0318] Example 13—Powder Characterization
[0319] The morphology, composition, and electrochemical properties of certain coated powders were evaluated using scanning electron microscopy (SEM), inductively coupled plasma optical emission spectroscopy (ICP-OES), and a Maccor instrument.
[0320] Figures 3A to 3C A series of scanning electron micrographs according to exemplary embodiments are shown, illustrating a base powder, a base powder coated with 0.1 wt% AlF3, and a base powder coated with 0.1 wt% Al2O3. The base powder corresponds to a powder containing Li. 1.02 Co 0.96 Mn 0.04 O2 particles. The powder before and after wet impregnation showed only minor differences. Compared to uncoated powder (i.e.... Figure 3A Compared to powder coating (i.e.) Figure 3B and Figure 3C The surface of the surface may appear fuzzy and rough, as indicated by stains or bumps.
[0321] The amounts of Al2O3 and AlF3 coated on the base powder sample were determined using ICP-OES. Tables 2 and 3 show the results of the wet impregnation of the base powder with Al2O3 and AlF3, respectively. The comparison between the target coating level and the measured values indicates that the measured values match their corresponding target values for a coating level of ≥0.2 wt% very well.
[0322] Table 2. ICP-OES results of Al2O3-coated and uncoated base powders
[0323]
[0324] Table 3. ICP-OES results of AlF3-coated and uncoated base powders
[0325]
[0326] Example 14
[0327] Electrochemical tests were performed on a 2032 coin half-cell, which exhibited a concentration of approximately 15 mg / cm³. 2 The cathode active material was loaded. The electrolyte used in the 2032 coin half-cell contained 1.2M LiPF6 with EC:EMC as the solvent, wherein the EC:EMC weight ratio was 3:7. The cell was placed on a Maccor Series 2000 tester and cycled at room temperature in constant current mode with a voltage window from 4.5V to 2.75V. A series of electrochemical tests for formation, rate, and cycling were performed at each voltage window. During the formation test, a constant current (0.2C) was applied to the cell during the charging process, followed by constant voltage charging until the current was equal to or less than 0.05C. Subsequently, the cell was discharged at a constant current (0.2C) until the discharge was complete. The charging and discharging of the cell were repeated three times. During the rate test, for all rate tests, the charging rate was fixed at 0.7C, followed by constant voltage charging until the current was equal to or less than 0.05C. Five different discharge rates of 0.1C, 0.2C, 0.5C, 1C, and 2C were applied until the cell was fully discharged. Three cycles were performed for each rate. Finally, 50 cycles were performed to investigate cycle life. The same charging conditions as those used for the rate tests were applied. The discharge rate was fixed at 0.5C for all cycles.
[0328] Here we show the base powder Li 1.04 Co 0.96 Mn 0.04 O2 and the two most frequently applied coating samples (Li 1.04 Co 0.96 Mn 0.04 O2-Al2O3 0.05 wt% and Li 1.04 Co 0.96 Mn0.04 Cyclic data for O2-AlF3 (0.1 wt%).
[0329] Figure 4 A graph showing data representing the performance of three coin half-cells (each incorporating a single cathode active material) during the first charge and discharge cycles, according to an exemplary embodiment, is presented. The single cathode active material for each of the three coin half-cells corresponds to the base powder Li. 1.04 Co 0.96 Mn 0.04 O2 (i.e., "HW168"), Li coated with 0.05 wt% Al2O3 1.04 Co 0.96 Mn 0.04 O2 (i.e., "HW168-Al2O3 0.05 wt%) and Li coated with 0.1 wt% AlF3 1.04 Co 0.96 Mn 0.04 O2 (i.e., "HW168-AlF3 0.1 wt%)). The performance of the three-coin half-cell is characterized by the following two bars: the leftmost bar indicates the first cycle charge capacity, and the rightmost bar indicates the first cycle discharge capacity.
[0330] exist Figure 4 In the study, the presence of a coating in the cathode active material slightly reduced the first-cycle charge and discharge capacity, as both the Al₂O₃-coated and AlF₃-coated variants showed a capacity reduction of 4 mAh / g compared to the uncoated variant. This value is higher than expected for such a small amount of coating. This reduction in capacity can be attributed to lithium loss during the coating process, as indicated by the ICP-OES data in Tables 3 and 4. However, Figure 4 The performance shown (which is the initial performance) does not represent the performance of the coin half-cell in subsequent charge and discharge cycles.
[0331] Figure 5 and Figure 6 The following is shown according to an exemplary implementation. Figure 4 A graph showing how the capacity of a three-coin half-cell changes with increasing cycles. Figure 7 and Figure 26 The following is shown according to an exemplary implementation. Figure 4 A graph showing the change in energy density of a three-coin half-cell with increasing cycles. Figure 5 and Figure 7 Corresponding to the rate test, and Figure 6 and Figure 8 Corresponding to lifespan testing.
[0332] Figure 5The results show that, up to a C rate of 1, the presence of the coating does not affect the introduction of Li. 1.04 Co 0.96 Mn 0.04 O2, Li coated with Al2O3 1.04 Co 0.96 Mn 0.04 O2 and Li coated with AlF3 1.04 Co 0.96 Mn 0.04 The performance of O2 in coin-sized half-cells is similar up to 1C (i.e., for C / 10, C / 5, C / 2, and 1C). This corresponds to Li coated with Al2O3. 1.04 Co 0.96 Mn 0.04 O2 coin half-cells show (relative) performance degradation at a rate of 2C.
[0333] Figure 6 The lifetime test is shown, and the beneficial effects of the coating are highlighted more clearly in this figure. Corresponding to the coated Li... 1.04 Co 0.96 Mn 0.04 The O2 variant of the coin half-cell showed relative performance compared to the uncoated Li. 1.04 Co 0.96 Mn 0.04 O2 exhibits improved capacity. Compared to coated Li... 1.04 Co 0.96 Mn 0.04 O2-related coin half-cells only lost 4-5 mAh / g.
[0334] Introducing uncoated Li 1.04 Co 0.96 Mn 0.04 The coin half-cell of O2 initially has a low capacity, i.e., relative to the introduction of coated Li. 1.04 Co 0.96 Mn 0.04 Those with O2 exhibit lower capacity because the coin half-cell has been cycled 19 times after aging and rate testing. This type of pre-aging, compared to those without pre-aging (i.e., those utilizing coated Li), results in lower capacity. 1.04 Co 0.96 Mn 0.04 The presence of O2 leads to faster degradation. After 26 lifetime cycle tests, more than 15 mAh / g of capacity was lost.
[0335] exist Figure 7 and Figure 8 Observed and about Figure 5 and Figure 6The same energy density trend was observed. However, compared to uncoated Li... 1.04 Co 0.96 Mn 0.04 The O2-related coin half-cell initially had a lower energy density than the coin half-cells of the two coated samples. Figure 7 and Figure 8 The energy density of the sample coated with AlF3 is higher than that of the sample coated with Al2O3.
[0336] Figure 9 and Figure 10 It shows the representation Figure 4 A graph showing the charging and discharging characteristics of each of the three coin half-cells. Figure 9 A rate test was shown, and Figure 10 Lifetime tests are shown. These characteristics confirm the advantages of the coating disclosed herein. Compared to introducing a base powder Li 1.04 Co 0.96 Mn 0.04 A coin-shaped half-cell of O2, introducing Li coated with Al2O3 and AlF3. 1.04 Co 0.96 Mn 0.04 The curve shape change of the coin half-cell of O2 is not obvious. In fact, corresponding to uncoated Li 1.04 Co 0.96 Mn 0.04 The variants of O2 showed a faster capacity decay with increasing cycle number.
[0337] Figure 11 and Figure 12 It shows the representation Figure 4 A graph showing the dQ / dV characteristic data for each of the three coin half-cells. Figure 11 A rate test was shown, and Figure 12 The lifetime test is shown. The curves in each figure are plotted for both the rate test and the lifetime test every 5 cycles. The decreasing peak at approximately 3.85 V characterizes the structural stability of the cathode active material in each coin half-cell during gradual cycling.
[0338] The degradation (i.e., structural instability) of the cathode active material is reflected by a shift and broadening of the peak towards lower voltages. During rate testing, this corresponds to the Li base powder... 1.04 Co 0.96 Mn 0.04The O2-coated coin cell showed the highest degradation, with a relatively fast shift and significant peak broadening at 3.85V, indicating a reduced peak spacing. In contrast, the coin cell corresponding to its coating variant showed a slower shift and less broadening. Peak shift and broadening were less pronounced during rate testing compared to lifetime testing. This behavior is attributed to cycling with lower amounts of lithium ions at progressively increasing charge / discharge rates. During lifetime testing, the coin cell incorporating baseline LiCoO2 showed further degradation, while the one incorporating Li... 1.04 Co 0.96 Mn 0.04 O2 and its coating variants showed almost no degradation.
[0339] Example 15—Cathode Active Material Obtained by Co-precipitation Method
[0340] A 3.5-liter stirred tank reactor was filled with distilled water and heated to 60°C. While stirring the distilled water at 1100 rpm, a nitrogen stream was introduced into the reactor. Manganese sulfate and cobalt sulfate were dissolved separately in the distilled water to prepare a first aqueous solution with a total concentration of 2.0 M and a predetermined molar ratio (i.e., [Mn]:[Co]). Representative examples of ratios include [Mn]:[Co] = 0.00:1.00, 0.04:0.96, 0.07:0.93, 0.10:0.90, 0.16:0.84, and 0.28:0.72. The first aqueous solution was continuously added dropwise to the distilled water in the reactor at a flow rate of 100 mL / h to prepare a combined aqueous solution. The pH of the combined aqueous solution was maintained at 11.5 using a pH controller connected to the pump by adding a second aqueous solution containing sodium hydroxide and ammonia. After 300 hours of operation, the particles nucleated and grew in the combined aqueous solution, forming the final precursor particles. The final precursor particles were then washed, filtered, and dried at 175°C for 12 hours.
[0341] The final precursor particles are used to form the constituent LiMn x Co 1-x The cathode active material of O2, where x and 1-x correspond to a predetermined molar ratio, i.e., [Mn]:[Co]=[x]:[1-x]. Solid-state reaction is carried out using Li2CO3 powder and final precursor particles. [Li]:[Mn]:[Co] is obtained using different molar ratios of Li2CO3 and final precursor particles. x Co 1-xCathode active materials with different ratios (i.e., the ratio of lithium to total transition metal content) were prepared. Li₂CO₃ powder and the final precursor particles were co-mixed in an orbital stirrer to prepare a mixed powder. After mixing, the mixed powder was transferred to an alumina tray and heated in flowing air at 700°C for 10 hours. The oven ramp rate was 5°C per minute. After heating at 700°C, the reacted mixed powder was placed in the oven and cooled to ambient temperature by natural heat loss. The resulting intermediate powder was ground with a mortar and pestle, sieved, and calcined in flowing air at 1050°C for 15 hours. The ramp rate was 5°C per minute, and after calcination, the resulting sintered powder was placed in an oven and cooled to ambient temperature by natural heat loss. The sintered powder was crushed, ground with a mortar and pestle, and sieved to prepare the cathode active material. The samples of the cathode active material were characterized by powder X-ray diffraction using a Bruker D8 (see [link to Bruker D8]). Figure 20 and Figure 21 ).
[0342] Representative examples of cathode active materials prepared by the above co-precipitation method include LiCoO2 and Li 0.987 Co 0.96 Mn 0.04 O2, Li 1.050 Co 0.96 Mn 0.04 O2, Li 1.074 Co 0.96 Mn 0.04 O2, Li 1.081 Co 0.96 Mn 0.04 O2, Li 1.089 Co 0.96 Mn 0.04 O2, Li 0.981 Co 0.93 Mn 0.07 O2, Li 1.050 Co 0.93 Mn 0.07 O2, Li 0.984 Co 0.90 Mn 0.10 O2, Li 1.065 Co 0.90 Mn 0.10 O2, Li 1.100 Co 0.90 Mn 0.10 O2, Li 1.110 Co 0.90 Mn 0.10 O2, Li 1.158 Co 0.90 Mn 0.10 O2, Li 0.975 Co0.84 Mn 0.16 O2, Li 1.050 Co 0.84 Mn 0.16 O2, Li 1.114 Co 0.84 Mn 0.16 O2, Li 0.994 Co 0.78 Mn 0.22 O2, Li 1.100 Co 0.78 Mn 0.22 O2, Li 1.197 Co 0.78 Mn 0.22 O2, Li 0.973 Co 0.72 Mn 0.28 O2, Li 1.087 Co 0.72 Mn 0.28 O2, Li 1.190 Co 0.72 Mn 0.28 O2 and Li 1.247 Co 0.72 Mn 0.28 O2.
[0343] Figure 19 Scanning electron microscopy (SEM) images of the cathode active material prepared according to the co-precipitation method described above are shown. The microscopy images represent secondary particles formed from densely sintered primary particles. Such densely sintered secondary particles are typically used in cathode active materials prepared by the co-precipitation method. The composition of the cathode active material corresponds to Li. 0.96 Co 0.93 Mn 0.07 O2, Li 0.98 Co 0.93 Mn 0.07 O2 and Li 1.00 Co 0.93 Mn 0.07 O2.
[0344] Figure 20 The X-ray powder diffraction pattern of the cathode active material represented by the following composition is shown: Li 1.074 Co 0.96 Mn 0.04 O2, Li 1.081 Co 0.96 Mn 0.04 O2, Li 1.089 Co 0.96 Mn 0.04 O2, Li 1.065 Co 0.90 Mn 0.10O2, Li 1.110 Co 0.90 Mn 0.10 O2, Li 1.158 Co 0.90 Mn 0.10 O2, Li 0.975 Co 0.84 Mn 0.16 O2, Li 1.050 Co 0.84 Mn 0.16 O2 and Li 1.114 Co 0.84 Mn 0.16 O2. These cathode active materials were prepared according to the co-precipitation method described above. Figure 20 In the diffraction pattern groups, the groups are arranged from bottom to top, with the bottom and top corresponding to increases in manganese content, i.e., from 0.04 to 0.10 to 0.16. However, within each group, the lithium to transition metal ratio (i.e., [Li] / [Mn]) is... x Co 1-x The peaks decrease in increments of three from bottom to top. The reference bars indicate the expected peaks of Li2MnO3, Co3O4, and LiMnO2, shown in pink, gray, and blue, respectively.
[0345] Figure 20 Most of the cathode active materials are single-phase. The absence of a peak near 2θ = 20° indicates the absence of Li₂MnO₃ in the cathode active materials. Furthermore, despite replacing Co with more Mn, the crystal structure of each cathode active material (as indicated by the space group) remains unchanged. However, for lower [Li] / [Mn] x Co 1-x ] value, i.e., Li 0.975 Co 0.84 Mn 0.16 O2, resulting in the stoichiometry of the M3O4 metal oxide phase (e.g., Co3O4).
[0346] Figure 21 The X-ray powder diffraction pattern of the cathode active material represented by the following composition is shown: Li 0.994 Co 0.78 Mn 0.22 O2, Li 1.100 Co 0.78 Mn 0.22 O2, Li 1.197 Co 0.78 Mn 0.22 O2, Li 0.973 Co 0.72 Mn 0.28 O2, Li 1.087 Co0.72 Mn 0.28 O2, Li 1.19 Co 0.72 Mn 0.28 O2 and Li 1.247 Co 0.72 Mn 0.28 O2 was used to prepare these cathode active materials according to the co-precipitation method described above. In Figure 3, the diffraction pattern groups are arranged from bottom to top, with the bottom and top corresponding to the increase in manganese content, i.e., from 0.22 to 0.26. However, in each group, the lithium to transition metal ratio (i.e., [Li] / [Mn]) is different. x Co 1-x The peaks decrease in increments of three from bottom to top. The reference bars shown indicate the expected peaks for Li2MnO3 and Co3O4.
[0347] exist Figure 21 In this study, the degree to which Mn replaced Co was higher than that of Co. Figure 20 However, the crystal structure of each cathode active material (as shown by the space group) is as follows: Li 0.994 Co 0.78 Mn 0.22 O2, Li 1.10 Co 0.78 Mn 0.22 O2, Li 0.973 Co 0.72 Mn 0.28 O2 and Li 1.087 Co 0.72 Mn 0.28 The diffraction pattern of O2 shows peaks near 2θ = 20°. These peaks indicate the presence of a small proportion of Li2MnO3 in these cathode active materials. However, in the [Li] / [Mn]... x Co 1-x The value of ] is close to 1+x, that is, Li 1.197 Co 0.78 Mn 0.22 O2 and Li 1.247 Co 0.72 Mn 0.28 The composition of O2 indicates that there are no peaks in the cathode active material. These cathode active materials are single-phase. The metric 1+x corresponds to xLi2MnO3·(1-x)LiCoO2 (i.e., Li...). 1+x Co 1-x Mn x O 2+x Ideal solid-solution stoichiometry.
[0348] Example 16—Cathode Active Material Obtained by Sol-Gel Method
[0349] A first aqueous solution of manganese acetate and cobalt acetate was prepared at a predetermined molar ratio (i.e., [Mn]:[Co]) and a total of 2 mol. The predetermined ratios include representative examples such as [Mn]:[Co] = 0.10:0.90, 0.16:0.84, 0.22:0.78, and 0.28:0.72. A second aqueous solution of citric acid was added to the first aqueous solution and mixed by magnetic stirring to prepare a combined solution. The combined solution was heated to 80°C to form a gel, which was then held at 80°C for 6 hours. The gel was then transferred to a box furnace and calcined at 350°C for 4 hours. After cooling, the resulting cake was ground with a mortar and pestle, sieved, and then calcined again at 900°C for 12 hours in flowing air. The ramp rate was 5°C per minute, and after calcination, the resulting cathode active material was placed in an oven to cool to ambient temperature by natural heat loss. The cathode active material samples were characterized using powder X-ray diffraction with a Bruker D8 (see [reference]). Figure 23 ).
[0350] Representative examples of cathode active materials prepared by the above sol-gel method include Li 1.131 Co 0.90 Mn 0.10 O2, Li 1.198 Co 0.84 Mn 0.16 O2, Li 1.241 Co 0.78 Mn 0.22 O2 and Li 1.301 Co 0.72 Mn 0.28 O2.
[0351] Figure 22 Scanning electron microscopy (SEM) images of the cathode active material prepared according to the sol-gel method described above are shown. The micrographs indicate that the size of the fine, lamellar agglomerates is less than 1 μm. This type of fine particle morphology is typical of cathode active materials prepared by the sol-gel method. The composition of the cathode active material corresponds to Li. 1.1 Co 0.1 Al 0.01 Mg 0.01 Mn0 .89 O2, and is Li 1.28 Co 0.258 Al 0.02 Mg 0.02 Co 0.68 O2.
[0352] Figure 23 The X-ray powder diffraction pattern of the cathode active material represented by the following composition is shown: Li 1.131 Co 0.90 Mn0.10 O2, Li 1.198 Co 0.84 Mn 0.16 O2, Li 1.241 Co 0.78 Mn 0.22 O2 and Li 1.301 Co 0.72 Mn 0.28 O2. These cathode active materials were prepared according to the sol-gel method described above. The cathode active materials are single-phase. The crystal structure of each cathode active material (as shown by the space group) is as follows: The absence of peaks near 2θ = 20° indicates a lack of Li₂MnO₃ in these cathode active materials. However, the peak separation near 2θ = 65° indicates a well-crystallized, layered structure.
[0353] Example 17—Battery Performance
[0354] Figure 24 Differential capacity curves for cathode active materials represented by the following compositions are shown: LiCoO2, Li 1.05 Co 0.96 Mn 0.04 O2, Li 1.05 Co 0.93 Mn 0.07 O2, Li 1.110 Co 0.90 Mn 0.10 O2 and Li 1.19 Co 0.72 Mn 0.28 These cathode active materials were prepared using the co-precipitation method described above. During the first charge-discharge cycle, the differential capacity of the 2032 coin half-cell was measured at a rate of C / 5. Figure 24 In the graph, the vertical axis represents a measure of dQ / dV, and the horizontal axis represents a measure of electrochemical potential or voltage. The irreversible phase transition peak of LiCoO2 appears at a potential of approximately 4.45 V. However, after replacing Co with Mn, the phase transition shifts to a potential of approximately 4.55 V, and the peak intensity decreases. This behavior indicates that substituting Co (e.g., replacing Co with Mn) can produce cathode active materials with high voltage stability.
[0355] Figure 25 Voltage characteristic curves for cathode active materials represented by the following composition are shown: Li 1.05 Co 0.96 Mn 0.04 O2, Li 1.05 Co 0.93 Mn 0.07 O2, Li 1.110 Co 0.90 Mn 0.10O2 and Li 1.19 Co 0.72 Mn 0.28 O2. These cathode active materials were prepared according to the co-precipitation method described above and then incorporated into a 2032 coin half-cell. The voltage characteristics correspond to the first charge-discharge cycle with a charge / discharge rate of C / 10 and a voltage window of 2.75–4.6V. Figure 25 In the graph, the vertical axis represents a measure of the electrochemical potential (i.e., V) of the coin half-cell, and the horizontal axis represents a measure of the accumulated capacity (i.e., mAh / g). High specific capacity (i.e., >150 mAh / g) and high average voltage (i.e., >3.7 V) were achieved for all compositions. For Li... 1.19 Co 0.72 Mn 0.28 For O2 cathode active materials, the plateau at approximately 4.5V in the first charging curve indicates the presence of an activation process for the Li2MnO3-like phase in the material.
[0356] Example 18—Adjusting Battery Performance
[0357] It should be understood that factors such as the substitution of Co (e.g., Co) 1-x-y M y Mn x ) and the lithium to Co ratio and its substitution (i.e., [Li] / [Co) 1-x-y M y Mn x The phase present in the cathode active material is affected. For example... Figures 20 to 21 and Figure 23 As has been confirmed, such factors can be selected to prepare single-phase cathode active materials (e.g. Crystal structure). Furthermore, such as Figure 24 and Figure 25 As has been confirmed, such factors can also be selected to improve battery performance (e.g., increase voltage stability).
[0358] Figure 26 An isopleth plot of the discharge energy density is shown, which varies with substitution (i.e., Co). 1-x Mn x The ratio of [Li] to [Co] is: 1-x Mn x The discharge energy density corresponds to the measurements of the 2032 coin half-cell obtained during the first cycle and at a charge / discharge rate of C / 10. The isopleth plots were generated through a combination of sample measurements and predictive modeling. The 2032 coin half-cell used a cathode active material prepared according to the sol-gel method described above (where 0 ≤ x ≤ 0.28). Figure 26There are two regions that indicate high energy density (i.e., >700 Wh / kg): [1] The first region has a Mn content of at most about 12% (i.e., x ≤ 0.12) and a ratio of at most about 1.15 (i.e., [Li] / [Co]). 1-x Mn x [1]≤1.15), and [2] the second region, the Mn content is higher than about 25% (i.e., x>0.25), and the ratio is higher than about 1.25 (i.e., [Li] / [Co] 1-x Mn x [>1.25].
[0359] Figure 27 This shows an isopleth plot of energy retention rate, which varies with substitution (i.e., Co). 1-x Mn x The ratio of [Li] to [Co] is: 1-x Mn x The energy retention rate corresponds to the measurement results of the 2032 coin half-cell obtained after 10 cycles and at a charge / discharge rate of C / 3. The isopleth plots were generated through a combination of sample measurements and predictive modeling. The 2032 coin half-cell used a cathode active material prepared according to the sol-gel method described above (where 0 ≤ x ≤ 0.28). Similar to... Figure 26 middle, Figure 27 There are two regions that indicate high energy density (i.e., >700 Wh / kg): [1] The first region has a Mn content of at most about 12% (i.e., x ≤ 0.12) and a ratio of at most about 1.15 (i.e., [Li] / [Co]). 1-x Mn x [1]≤1.15), and [2] the second region, the Mn content is higher than about 25% (i.e., x>0.25), and the ratio is higher than about 1.25 (i.e., [Li] / [Co] 1-x Mn x [>1.25].
[0360] Example 19
[0361] Li α Co 1-x-y Al y Mn x O δ Four samples were fabricated into coin batteries using Li metal anodes and cycled at a charge / discharge rate of C / 5 at 2.75–4.5 V. The four samples correspond to x = 0.01, 0.02, 0.03, and 0.04, where α = 1.0; y ranges from 0.001 to 0.003; and δ is approximately 2.0. Figure 28 and Figure 29The graph shows the derivative of differential capacity with respect to electrochemical potential (i.e., dQ / dV versus V), illustrating the effect of Mn and Li content on cell performance. During charging and discharging at the LiCoO2 cathode, the phase transition from the hexagonal phase to the monoclinic phase occurs between 4.0 and 4.3 V (see [link to diagram]). Figure 29 Mn substitution at x = 0.01 also results in a phase transition (see [link]). Figure 28 Phase transitions lead to lattice volume expansion, which can contribute to electrode capacity decay. In this case, replacing Co with Mn in a proportion greater than x = 0.01 mitigates the phase transition, such as... Figure 28 The composition for x = 0.02, 0.03, and 0.04 is shown in the figure.
[0362] Phase transitions also depend on the Li content in the compound. When considering, for example, in Li... α Co 0.97 Mn 0.03 When Mn is substituted in O2, the phase transition can be mitigated if α ≥ 1.0. Figure 29 As shown, as the Li content increases from 0.977 to 1.014, the characteristic phase transition peak in the dQ / dV curve between 4.0 and 4.3 V decreases to a flat line at α = 1.014.
[0363] On the other hand, the beneficial effects of excess Li are limited by its influence on volumetric energy density and retention. Figure 30 The figure shows that during cycling at a rate of C / 5 between 2.75 and 4.5 V, Li α Co 0.97 Mn 0.03 The effect of Li content in O2 on discharge energy. The stoichiometric composition, α = 1.003, showed a maximum energy of 754 Wh / g, with a loss of approximately 8% of this energy over 25 cycles. The Li-rich sample (i.e., α = 1.014) had a similar maximum energy but lost 10% of that energy. The substoichiometric composition (i.e., α < 1.0) showed even lower energy. This behavior, along with repeated testing with 2% Mn (i.e., x = 0.02), indicates that optimal energy and energy retention were achieved at a lithium content where α is approximately 1.00. The compositional values of each metal in the material were determined by high-precision ICP-OES analysis, particularly the measurement of the lithium content (i.e., α).
[0364] Similar electrochemical measurements (not shown) also demonstrated the effect of aluminum content on reducing the hexagonal-to-monoclinic phase transition. This is because aluminum is replaced by another Li. α Co 1-x-y Al y Mn x O δ With a fixed composition, phase transitions are suppressed.
[0365] There may be a, x, and y that result in volumetric energy, energy retention, and phase transition inhibition. From this examination, it was determined that any substitution of Mn, Al, and Li, or additional or other elements that can be substituted into this structure, in a total amount ≥3% (i.e., x ≥ 0.03), would weaken the hexagonal-to-monoclinic transition during 4.0–4.3 V. It also appears that additional elements are correlated with the sum of their oxidation states, i.e., Mn… 4+ Al 3+ and Li + The combined amounts should reach a certain level to prevent a phase transition. This is because it has been observed that different Li stoichiometry is required for a given Mn content to prevent a phase transition.
[0366] Example 20
[0367] like Figure 31 As shown, the optimal Mn content (i.e., x) is determined to be between x = 0.02 and x = 0.04, which allows Mn-substituted LiCoO2 to achieve the highest volumetric energy density and energy retention during cycling at a C / 5 rate between 2.75 and 4.5 V. Battery cells with similar Li and Al contents, comprising three compositions with x = 0.02, 0.03, and 0.04, were cycled at a C / 5 rate from 2.75 to 4.5 V. The composition corresponding to x = 0.03, although exhibiting a slightly lower initial energy compared to x = 0.02, showed the highest energy retention.
[0368] Example 21—Nuclear Magnetic Resonance
[0369] solid state 6 Li nuclear magnetic resonance (NMR) measurements identified Li α Co 1-x Mn x O δ Mn-Mn aggregates exist within the material. These aggregates ultimately lead to the formation of Li₂MnO₃ as the increased Mn and Li content exceeds the phase limits of the Li-rich composition. Unwilling to be confined to a specific mechanism or mode of operation, the Mn aggregates stabilize the cathode structure, which provides the material described herein with the high voltage stability shown in any electrochemical test.
[0370] However, HR-XRD and NMR do not show any Li₂MnO₃ formation in the composition considered in this study. No new phase peaks corresponding to Li₂MnO₃ are present in either the HR-XRD or NMR spectra. Figure 32Comparative results for Mn-substituted LiCoO2 at x = 0.03 and x = 0.04 are shown. NMR quantification of the specified resonance states shows that the accumulation of manganese at x = 0.04 is twice that at x = 0.03, rather than the expected 25% increase. Although manganese substitution is considered to be for stabilizing LiCoO2... The crystal structure has a large manganese aggregate that tends to introduce lithium into the transition metal (TM) layer. This results in a vacancy in the transition metal layer that weakens the stability of the crystal structure when lithium is extracted from the crystal structure at a higher voltage (4.5V) if lithium in the transition metal layer falls into the lithium layer.
[0371] Example 22—Adding Aluminum
[0372] Preparation of Li with composition 1.01 Co 0.97-y Al y Mn 0.03 O δ Three cathode active materials were used, with the contents of Li and Mn fixed at 1.01 and 0.03, respectively, while the Al contents varied to 0.077 wt%, 0.159 wt%, and 0.760 wt%. The cathode active materials were tested in half-cells at a cycling rate of 2.75–4.5 V and C / 5. Figure 33 The results show that the discharge energy decreases due to increased Al substitution. However, the energy retention improves with increasing Al content, with a maximum Al substitution of 0.76 wt% exhibiting the best discharge energy after 25 cycles.
[0373] Example 23—Particle Morphology
[0374] To achieve stability and high energy density, Li can be heated at sufficient temperatures. α Co 1-x-y Al y Mn x O δ The cathode active material is processed for a sufficient time so that the secondary particles contain dense single crystals (i.e., primary particles). These dense single crystals impart high strength to withstand the rolling process during electrode fabrication and cell assembly. Figures 34A to 34B and Figures 35A to 35B The optimal treatment is shown to achieve the effect of high-strength particles.
[0375] When the precursor powder is treated at a sufficient temperature for a sufficient time, it can be further sintered. Figure 34A The polycrystalline structure seen in the example obtains, for example, Figure 34B Larger and stronger grains are more resistant to breakage. This improved strength is achieved through... Figures 35A to 35B As shown in the figure. Due to partial interconnection caused by sintering, at 1050°C ( Figure 35AThe size distribution of the precursor powder calcined under these conditions grew from 18 μm to 22 μm. When the powder was granulated and the particles fractured under pressure (i.e., simulating electrode laminate calendering), the particle size distribution decreased to a bimodal distribution due to the breaking of particle-particle bonds (i.e., between primary particles), and the particles broke into smaller primary grains. However, when the temperature was increased to 1085 °C for the same processing time, the larger single grains sintered together during processing fractured back to the initial precursor size but did not fracture further. This strength prevented the formation of new surfaces, such as those not protected by the Al2O3 coating and subjected to interaction with the electrode.
[0376] Example 24—Energy Retention Rate
[0377] Calcination temperature affects not only particle strength but also the energy retention rate of the cathode active material used as an electrode. As the calcination temperature increases, the energy retention rate also increases to a maximum value between 1075-1080℃. Figure 36 After compaction of powder calcined at an increased temperature, the change in surface area stabilizes with increasing particle strength, and no new surface is exposed due to particle crushing. Figure 36 This illustrates the correlation between the strength (stable surface area change) of the cathode active material and its energy retention rate. Figure 36 In the process, the cathode active material has a composition in which the ratio of lithium to transition metal (Li / TM) is 1.01 (i.e., α = 1.01 and y = 0).
[0378] The discharge capacity and coulombic efficiency of the cathode material in the first cycle are also related to the calcination temperature. Figure 37 This relationship is illustrated. The initial discharge capacity and initial energy decrease effectively as the calcination temperature of the material increases from 1050°C to 1092°C. Coulombic efficiency is a measure of the amount of Li inserted back into the cathode during the first discharge, showing the portion of Li eliminated from future charge / discharge cycles. Maximum efficiency occurs at 1080°C, while the capacity related to particle strength is optimally between 1070 and 1080°C. This sensitivity to calcination temperature is part of the novelty of the proposed invention, as it is shown to affect particle strength, energy retention, Li content, cycle life, material capacity, and energy.
[0379] Example 25—Thermal Stability
[0380] The increased energy of Li-ion battery materials also brings with it a greater risk of accidental energy release, such as heat causing the battery cell to catch fire. Differential scanning calorimetry (DSC) of the cathode active material during charging and exposure to the electrodes helps determine the risk of thermal failure. Figure 38DSC measurements are shown for five Mn-substituted LiCoO2 compositions with Mn content ranging from 1 to 7 mol% (i.e., x = 0.01–0.07). Compared to commercial LCO (i.e., LiCoO2), the 1% Mn composition (i.e., x = 0.01) shows a lower onset temperature in exothermic reactions that generate more heat. However, with increasing Mn content, the onset temperature of the reaction increases, and the total heat released decreases until Mn reaches 7%. After Mn = 4%, the onset temperature increases, but the heat release of the reaction begins to increase again. These values are listed in Table 4. Based on the DSC measurements, the optimal Mn substitution is between 3 and 4 mol% Mn (i.e., 0.03 ≤ x ≤ 0.04).
[0381] Table 4. Summary of DSC Measurement Results
[0382]
[0383] Example 26—Lattice Parameters
[0384] The Li content (i.e., α), which is crucial to material properties, is correlated with variations in the c-lattice parameters of the crystal structure, as shown in the figure. Figure 39 As shown, based on the Mn content (as Mn increases, the c-lattice parameter also increases), the Li content will decrease the c-lattice value with increasing Li content. It is also shown that as the Mn content increases, the material can accommodate excess lithium while maintaining [its properties] in the cathode active material. The ability to determine crystal structures is increased. LiCo (1-x) This phase diagram for the MnO2 system provides the optimal Li addition without the formation of a secondary phase.
[0385] Example 27—Raman Spectroscopy
[0386] Raman spectra of layered LiCoO2 and Mn-substituted LiCoO2 (i.e., x = 0.04 and 0.07) in Figure 40 The image shows the Raman spectrum obtained using 785 nm photon excitation. Based on factor group analysis, the layered structure exhibits... The crystal structure of LiCoO2 is expected to exhibit two Raman active modes, namely, one at approximately 596 cm⁻¹. -1 The location is A1. g Symmetry (due to symmetrical oxygen vibrations along the c-axis), and another at approximately 486 cm. -1 The location is E. g Symmetry (due to two degenerate symmetric oxygen vibrations in the a / b crystal plane). With the addition of Mn to the structure, new Raman scattering features appear above 596 cm⁻¹. -1 belt and below 486cm -1At the frequency of the band. This new scattering originates from the Mn-O bond stretching vibration, which is associated with various Mn-Co-Li occupancy sites formed throughout the transition metal layer. The relative strength of the bonds induced by these new Mn-O vibrations increases with increasing Mn substitution. 320 cm⁻¹ -1 The nearby bands are from the CaF2 window, through which the Raman spectra are obtained.
[0387] Example 28—Oxidative Stability
[0388] Figure 41 The oxidation stability results are shown in the figure compared to 7% Mn substitution (i.e., x = 0.07) versus 4% Mn substitution (i.e., x = 0.04). The half-cell was charged from open-circuit value to 4.65V and then cycled between 4.0V and 4.65V in continuous cycle operation. The 52nd cycle was a full cycle performed between 2.75V and 4.65V. Figure 41 In the figure, at the 52nd cycle, the discharge capacity versus the lithium to transition metal ratio (i.e., α, where y = 0) curve shows that the optimal capacity occurs near the Li content (α). Under these cycling conditions, the substitution with x = 0.07 maintains a higher capacity after 52 cycles compared to x = 0.04, indicating better capacity retention under these conditions.
[0389] exist Figure 42 In the middle, the introduction of Li was plotted. 1.00 Co 0.93-y Al y Mn 0.07 O δ The dQ / dV of the half-cell with cathode active material and the introduction of Li 1.025 Co 0.96-y Al y Mn 0.04 O δ The dQ / dV of the half-cell of the cathode active material. Figure 42 The degradation process of the x = 0.07 sample at a high voltage of approximately 4.53 V is shown. However, another degradation peak is evident at 4.47 V for the x = 0.04 sample, indicating a possible instability or additional phase transition. Such instability or phase transition can lead to structural transformations during cycling. Note that this degradation process lacks its own charging peak, which suggests irreversibility and therefore indicates internal capacity retention when cycling to a higher voltage of 4.65 V. Figure 41 The discussion.
[0390] Example 29—Capacity and Coulombic Efficiency
[0391] The capacity of the first cycle is shown in Figure 43In the figure, the first cycle charge and discharge values, along with the calculated coulombic efficiency, are plotted as a function of the lithium to transition metal ratio (i.e., α, where y = 0). The coulombic efficiency shows better improvement at approximate stoichiometric values. A larger α value allows more Li to be extracted from the cathode active material. However, conversely, higher Li content results in lower discharge capacity. Therefore, the optimal α was investigated.
[0392] Example 30—X-ray Absorption
[0393] Based on the X-ray absorption (XAS) results of all compounds in the entire tandem (not shown here), for all α values in the Mn-substituted LiCoO2 sample, Co is in the +3 oxidation state and Mn is in the +4 oxidation state. Therefore, the calculated stoichiometry is Li 0.983 Co 0.914 Mn 0.069 O2, and Li is insufficient in the Li layer. Removing Li cations from the Li layer to satisfy the transition metal layer leads to Li 0.966 [Li 0.017 Co 0.914 Mn 0.069 O2. (Note that the values of Li, Co, and Mn in parentheses total one.) For the purposes of this invention, we further differentiate the material into having approximately 5% Li (insufficient) in the Li layer and a small amount of Li in the TM layer to bond with Mn, thereby forming Mn-Li-Mn domains to replace the Co-Co-Co domains. These Mn-Li-Mn domains have charge compensation and are key to the stability of the resulting LiMn2 lattice. However, the size of these units is constrained as suggested by density functional theory (DFT) calculations (not shown) and shows greater stability in the mode than under the cyclic condition described above at x = 0.04.
[0394] In the foregoing description, the specific naming used for illustrative purposes provides a thorough understanding of the described embodiments. However, it will be apparent to those skilled in the art that these specific details are not required to practice the described embodiments. Therefore, the foregoing description of specific embodiments described herein is presented for illustrative and descriptive purposes. They are not intended to be exhaustive or to limit the embodiments to the precise forms disclosed. It will be apparent to those skilled in the art that many modifications and variations are possible in light of the foregoing teachings.
Claims
1. A powder comprising particles, said particles comprising a compound represented by formula (Va): ( x )[Li2MnO3] • (1- x )[LiCoO2] (Va) Where 0 < x ≤ 0.10, and wherein the compound remains a single phase and has a triangular shape. Crystal structure, The average diameter of the particles is at least 5 µm and less than or equal to 30 µm; The particles include secondary particles, each of which comprises a plurality of primary particles sintered together. At least 30% of the average secondary particles are formed from a single primary particle; and The average diameter of the secondary particles is at least 20 µm.
2. A cathode active material comprising the powder according to claim 1.
3. A cathode, comprising a cathode current collector and a cathode active material according to claim 2.
4. A battery cell, comprising: The anode includes an anode current collector and an anode active material disposed on the anode current collector; as well as The cathode according to claim 3.
5. A portable electronic device, comprising: A set of components powered by a battery pack, the battery pack including the battery cells according to claim 4.